Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Faunal and environmental continuity in Middle to Late Pleistocene Sumatra - Benyamin P. Shidqi; Mathew Stewart; Gilbert J. Price; Julien Louys (Quaternary Science Reviews, 2026)

Intramolecular carbon isotope fractionations of acetate associated with glucose metabolism in Escherichia coli using gas chromatography orbitrap-mass spectrometry (GC Orbitrap-MS) - Youki J. Sato; Juliana K. Drozd; Elliott P. Mueller; Allison A. Baczynski; Alexis Gilbert; Katherine H. Freeman (Organic Geochemistry, 2026)

Occurrence and risk assessment of antibiotic residues in Mediterranean olive grove soils with different management: an EU-wide pilot study - Andrés J. Rascón; Alfonso Fernández-García; David Moreno-Gónzalez; Bienvenida Gilbert-López; Antonio J. Manzaneda; Juan F. García-Reyes (Environmental Research, 2026)

Moraxella species isolated from blood cultures in Europe (MORAXEu): a multicentre study of epidemiology and antimicrobial susceptibility with complementary phylogenomic analysis of publicly available genomes - Tone Tønjum; Vinicius da Silva Franklin-Duarte; Johan Christian Berild; Konstantina Gartzonika; Eirini Christaki; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Nikolaos Giormezis; Gergana Lengerova; Yordan Kalchev; Ana Budimir; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Interaction among GLP-1 signaling-related genetic variants suggests contribution to the control of appetitive traits among preadolescents - Timothy J. Renier; Diane Gilbert-Diamond; Lee M. Kaplan; Jiang Gui (Appetite, 2026)

Double-edged dispersal: animal-mediated transport in the Anthropocene - Andrew J. Abraham; Ethan S. Duvall; Eva Moracho; Maria J. Ruiz-López; Lola Gilbert; Diego Ellis-Soto; Tomos Prys-Jones; Emma-Liina Marjakangas (Trends in Ecology & Evolution, 2026)

Heart rate and sub-blubber temperature in harbour seals (Phoca vitulina) measured during the moult and post-moult using implantable loggers - W. D. Paterson; L. L. Chaise; S. E. Moss; R. Milne; C. Gilbert; J. I. Currie; D. Thompson; D. J. McCafferty (Journal of Comparative Physiology B, 2026)
The moult represents an important seasonal change in the physiology of phocid seals. However, physiological measurements are challenging due to the impracticalities of instrumenting moulting animals. The aim of this study was (i) to assess the feasibility of a long-term deployment of fully implantable loggers to measure heart rate (HR) and sub-blubber temperature (T b ) in harbour seals ( Phoca vitulina ) and (ii) to compare HR and T b during moult and post-moult periods. Loggers were surgically implanted on an adult and sub-adult harbour seal in captivity. Animals healed quickly from surgery and loggers provided 65 days of continuous data before removal of the device. Results showed that in the adult when hauled out and in the water HR was lower during the moult compared with the post-moult. For the sub-adult, HR while in the water was also higher during the post-moult, however, when hauled out there was no difference in HR between the moult and post-moult periods. When hauled out, T b was greater for both animals during the moult compared with the post-moult. During haulout events, T b increased over time in both periods and T b in both animals was lower during post moult compared to the moult period. In the sub-adult, T b decreased with time in the water during the moult but showed little change during the post-moult period, whereas no temporal change was evident in the adult during either period. This study demonstrated that fully implantable loggers are a useful research tool allowing measurement of physiological parameters that are otherwise difficult to measure in pinnipeds. Physiological measurements suggested that the requirement to maintain higher skin temperature for hair growth during the moult was offset by lower metabolism to save energy in water, and on land in the case of adults. However, a decrease in body temperature with time in water in the sub-adult indicated that a smaller body size and less well-developed blubber layer is not as effective in reducing heat loss compared to adults. Future physio-logging on pinnipeds throughout their annual lifecycle may therefore benefit from similar techniques used to implant loggers.

Assessment of Sorbitol as a Pharmaceutical Excipient in Oral Liquid Pediatric Formulations Submitted to the U.S. FDA - Gelareh A. Abulwerdi; Brianna Cote; Susan Abdel-Rahman; Elimika Pfuma Fletcher; Gilbert J. Burckart (The AAPS Journal, 2026)

Lasting impacts of sublethal prepupal heatwaves on fertility-related traits of the solitary bee Osmia bicornis - Jamie L. Smith; Elizabeth J. Duncan; James D.J. Gilbert (Journal of Thermal Biology, 2026)

Logging impact on giant herb density and reproductive strategies in central African moist forests - Juliette Picard; Victoire Jessica Ngambe; Olivier J. Hardy; Chauvelin Douh; Vivien Rossi; Pierre Couteron; Eric Forni; Jean-Joël Loumeto; Belvina Chardène Mabengo; Gilbert Nsongola; Yorick van Hoef; Maxime Réjou-Méchain (Forest Ecology and Management, 2026)

Phytochemical profiling and therapeutic potential of lemon-scented tea tree (Leptospermum petersonii) - Phuong Lan Hoang; Trong Duc Tran; Jayne Gilbert; Jennette Sakoff; Christopher J. Scarlett; Quan Van Vuong (Biocatalysis and Agricultural Biotechnology, 2026)

Confocal laser endomicroscopy: exploring endometrial image quality in relation to the oestrous cycle of mares - K. Gallacher; L. Woolford; R.O. Gilbert; L.C. Santos; J. McLeod; M. Hebart; G. Ferlini Agne; S. du Preez; K.L. Kind (Journal of Equine Veterinary Science, 2026)

Chemicals from Entada abyssinica stem bark inhibit acetylcholinesterase and nitric oxide production in LPS-stimulated RAW264.7 macrophages - Raduis Melong; Ache Roland Ndifor; Vanneck Bedel Tatsinda Tsapi; Armelle Tsamo Tontsa; Jean Paul Dzoyem; Jacobus N. Eloff; Lyndy J. McGaw; Gilbert Deccaux Wabo Fotso Kapche (South African Journal of Botany, 2026)

Effect of Incentivizing Pediatric Studies on the Development of Pediatric-Friendly Formulations - Susan M. Abdel-Rahman; Gilbert J. Burckart (The AAPS Journal, 2026)

PQRI Workshop: Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development - Gilbert J. Burckart; Susan Abdel-Rahman; Caleb Choi; M. Petrea Cober; James E. Cummins; Nikoletta Fotaki; Daniel Gonzalez; David Harris; Neil Parrott; Hardikkumar Patel; Fang Wu; Andreas Abend (The AAPS Journal, 2026)
In February of 2024, the Product Quality Research Institute held a virtual workshop entitled “Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development.” The workshop covered a range of topics related to pediatric formulation development and testing, including dissolution testing and applications to modeling drug absorption in developing pediatric patients. Workshop speakers reviewed the progress that has been made to advance our understanding of ontogeny related processes that drive interactions with product formulations and inform pediatric product development. They discussed recently constructed pediatric biorelevant models that provide more realistic information about drug dissolution in pediatric patients and their use in physiologically based models to produce data for regulatory submissions. Despite the progress, opportunities remain to expand the fund of knowledge on pediatric absorptive processes that will support the development of pediatric-friendly drug formulations. Graphical Abstract

Unlearned responses of chicks, Gallus gallus domesticus, towards aposematic insect-like stimuli - Christopher H. Taylor; David J.G. Watson; Francis Gilbert; David J. Pritchard; John Skelhorn; Tom Reader (Animal Behaviour, 2026)

Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

The European Biophysics Journal Prizes 2025: Recognising biophysical science at sub-cellular, cellular and tissue levels of organisation - Robert J. C. Gilbert (European Biophysics Journal, 2026)
The European Biophysics Journal Prizes for 2025, awarded at the European Biophysical Societies Association (EBSA) Congress in Rome last July, recognised three of the outstanding papers published by the Journal in 2022 and 2023. In making these awards, the Journal and EBSA again sought to recognise publications which were already proving their impact. The studies recognised are diverse and highlight the vitality of biophysical science in the 2020s. They concern studies of (i) synaptic vesicles undergoing glutamate uptake, (ii) red blood cells under pressure and the effects of mechanically triggered calcium influx, and (iii) how ciliary beating, the resulting wave effects and downstream transport processes interrelate in trachea. As such these Prizes recognise excellent biophysical science at sub-cellular, cellular and tissue levels of organisation.

Heterogeneity, Productivity, and Migration Drive Continental Evenness Patterns of Bird Assemblages - Neil A. Gilbert; Natalie Queally; Jacob C. Cooper; Harold N. Eyster; Peter J. Williams (Global Ecology and Biogeography, 2026)
Aim Evenness quantifies similarities in abundances among species in an assemblage and may influence processes such as species coexistence and the supply of ecosystem services. Previous work has failed to identify generalised patterns of how productivity and habitat heterogeneity influence evenness and moreover has not considered seasonal variation in evenness arising from migration. Therefore, our goal was to quantify the interplay of productivity, habitat heterogeneity, and migration on evenness patterns of bird assemblages. Location Contiguous United States. Time Period Contemporary. Group Birds (613 species). Methods Using relative abundance maps from eBird, we computed evenness of bird assemblages for 27 × 27 km grid cells at weekly temporal resolution. We used generalized linear mixed‐effects models to evaluate the influences of productivity (normalized difference vegetation index), habitat heterogeneity (Shannon diversity of land cover), and the dominance of migratory species on evenness. Results Productivity and heterogeneity interacted to influence evenness such that there was a positive productivity–evenness relationship in high‐heterogeneity landscapes but no relationship in low‐heterogeneity landscapes. Evenness was highest during the pre‐breeding and breeding seasons when migratory taxa were present, but a high dominance of migrants reduced evenness and generally dampened evenness–productivity relationships. Main Conclusions Evenness increased with productivity in high‐heterogeneity—but not low‐heterogeneity—landscapes, indicating that hypotheses relating to energy availability and niche partitioning should be considered jointly. Higher evenness during the growing season likely reflects the presence of low‐abundance migrant taxa, whereas the negative effects of migrant dominance on evenness are likely driven by one or few high‐abundance species. The dampening effect of migrant dominance on evenness–productivity relationships in many situations supports the notion that migrants concentrate in high‐productivity landscapes.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

3D-Bioprinted Urinary Catheters Enable Sustained Probiotic Recovery Under Flow and Improve Bladder Colonization In Vivo - Anthony J. Kyser; Arielle Greiner; Victoria Harris; Rudra Patel; Hermann B. Frieboes; Nicole M. Gilbert (Probiotics and Antimicrobial Proteins, 2025)

Shade tree species composition in a cacao (Theobroma cacao L.) agroecosystem in Ghana - Jacob Danso; Gilbert J. Anim-Kwapong; Sampson Konlan (Agroforestry Systems, 2025)

Persistent Genomic Erosion in Whooping Cranes Despite Demographic Recovery - Claudia Fontsere; Samuel A. Speak; Andrew J. Caven; Juan Antonio Rodríguez; Xuejing Wang; Carolina Pacheco; Molly Cassatt‐Johnstone; Georgette Femerling; Brigid Maloney; Jennifer Balacco; Joanna Collins; Ying Sims; et al. (Molecular Ecology, 2025)
Integrating in‐situ (wild) and ex‐situ (captive) conservation efforts can mitigate genetic diversity loss and help prevent extinction of endangered wild populations. The whooping crane ( Grus americana ) experienced severe population declines in the 18th century, culminating in a collapse to ~20 individuals by 1944. Legal protections and conservation actions have since increased the census population from a stock of 16 individuals to approximately 840 individuals, yet the impact on genomic diversity remains unclear. We analysed the temporal dynamics of genomic erosion by sequencing a high‐quality reference genome, and re‐sequencing 16 historical (years 1867–1893) and 37 modern (2007–2020) genomes, including wild individuals and four generations of captive‐bred individuals. Genomic demographic reconstructions reveal a steady decline, accelerating over the past 300 years with the European settlement of North America. Temporal genomic analyses show that despite demographic recovery, the species has lost 70% of its historical genetic diversity and has increased its inbreeding. Although the modern population bottleneck reduced the ancestral genetic load, modern populations possess more realised load than masked load, possibly resulting in a chronic loss of fitness. Integrating pedigree and genomic data, we underscore the role of breeding management in reducing recent inbreeding. Yet ongoing heterozygosity loss, load accumulation, and persistent effects of historical inbreeding (i.e., background inbreeding) argue against the species' downlisting from its current Endangered status on the IUCN Red List and the Endangered Species Act. The presence of private genetic variation in wild and captive populations suggests that wild‐captive crosses could enhance genetic diversity and reduce the realised load. Our findings emphasise the role of genomics in informing conservation management and policy.

The state and fate of noble metals in bornite and digenite - Samuel A. King; Cristiana L. Ciobanu; Nigel J. Cook; Ashley D. Slattery; Sarah E. Gilbert; J. Richard Kyle; Kathy Ehrig; Jie Yao (Lithos, 2025)

Rugged LC-MS/MS method for the large-scale monitoring of glyphosate and other highly polar pesticides in soils across European Union olive orchards - Alfonso Fernández-García; David Moreno-González; Andrés J. Rascón; Ana B. Martínez-Piernas; Bienvenida Gilbert-López; Antonio J. Manzaneda; Juan F. García-Reyes (Environmental Pollution, 2025)

Volcanoes to vugs: Demonstrating a FAIR geochemistry framework with a diverse application of major and trace element data through the AuScope EarthBank platform - Angus L. Nixon; Samuel C. Boone; Yoann Gréau; Fabian Kohlmann; Moritz Theile; Wayne Noble; Alexander Prent; John Foden; Steven Barnes; Ashlea N. Wainwright; Benjamin Wade; Karsten Goemann; et al. (Chemical Geology, 2025)

Climate Consideration in Environmental Effects Analyses on Federal Public Lands in the United States - Sarah E. Whipple; Sarah K. Carter; Tait K. Rutherford; Samuel E. Jordan; Richard J. Lehrter; Christopher T. Domschke; Megan A. Gilbert; Julian Reyes; Ella M. Samuel; Karen M. Schank; John C. Tull; David J. A. Wood (Environmental Management, 2025)

Macroinvertebrate metacommunity in mediterranean mountain ponds (south of Spain) - Juan Diego Gilbert; Francisco J. Márquez; Fernando Ortega; Francisco Guerrero (Biodiversity and Conservation, 2025)
Mediterranean mountain ponds are excellent model systems for studying aquatic community changes and their underlaying mechanism. Their location within mountain landscapes results in isolated and poorly connected ponds. Furthermore, these dynamics ecosystems exhibit regional variation in environmental and spatial characteristics, making them ideal island ecosystems for metacommunities studies. This study investigates the influence of environmental and spatial factors on macroinvertebrate metacommunity structure in 23 isolated Mediterranean mountain ponds in Andalusia (south Spain). Macroinvertebrate combined pattern-based (Elements of Metacommunity Structure) and mechanistic (Redundancy Analysis and variation partitioning) approaches were employed to examine non-random distribution patterns in macroinvertebrates metacommunity structure. Additionally, by classifying macroinvertebrates into functional traits groups, allowed for an assessment of how different trait-based assemblages responded to these environmental and spatial drivers, providing a more nuanced understanding of community assembly. Results revealed a nested species distribution pattern, with species-poor ponds as subsets of richer ones. Redundancy Analysis identified hydroperiod and pond size as important environmental drivers, while fine-scale spatial variables had a greater influence than broad-scale ones. Although environmental factors explained more variation overall, no strong direct relationship with environmental variables was observed. The results suggests that nested patterns are driven by a combination of biogeographical processes, local environmental factors (pond size, hydroperiod), and fine-scale spatial structure. These findings emphasize the importance of considering habitat heterogeneity, connectivity, and regional species pools for effective conservation and management strategies of these pond ecosystems. Conservation efforts should prioritize maintaining connectivity between ponds and preserving those with high species richness to ensure the long-term persistence of macroinvertebrate metacommunities.

Arctic lake trout ( Salvelinus namaycush ) show evidence of seasonal acclimation of cardiac adrenergic sensitivity but not heat tolerance - Emily P. Williams; Les N. Harris; Jean‐Sébastien Moore; Ella K. Middleton; Shira A. Berkelhammer; Ben Speers‐Roesch; Matthew J. H. Gilbert (Journal of Fish Biology, 2025)
Many Arctic fishes experience prolonged periods of extreme cold and large thermal variation over both rapid and seasonal time scales which challenge critical physiological functions. In the central Canadian Arctic, we caught wild adult lake trout ( Salvelinus namaycush ) acclimatized to winter and summer temperatures to determine the extent to which they seasonally adjust cardiac thermal performance and adrenergic control. We assessed the intrinsic and maximum heart rate ( f Hint and f Hmax ) of anaesthetised fish through cholinergic blockade and either adrenergic blockade ( f Hint ) or stimulation ( f Hmax ) during acute warming. Contrary to expectations, S. namaycush showed largely consistent heart rate responses to acute warming between seasons and adrenergic treatments. The f Hmax increased with acute warming and reached a peak (peak f H ) of 83 and 93 beats min −1 at temperatures ( T peak ) of 19.6 and 20°C and arrhythmia occurred at temperatures ( T arr ) of 22.7 and 22.3°C in winter and summer, respectively. However, in the winter, adrenergic stimulation was important to achieve peak f H at high temperatures; adrenergic blockade in winter did not affect T peak (18.3°C) or T arr (21°C) but lowered peak f H to only 68 beats min −1 ( p f H , when compared at common, cool to moderate temperatures, winter acclimated fish did exhibit slower atrioventricular conduction (longer PR interval), slower ventricular depolarization (longer QRS duration) and a shorter overall systolic duration (lower QT interval). Overall, S. namaycush exhibited no seasonal plasticity in cardiac thermal tolerance and modest seasonal changes in adrenergic control at high temperatures and in cardiac electrical activity. This limited thermal plasticity may constrain their ability to cope with seasonally distinct thermal challenges including extreme heat events and increase their reliance on other coping or avoidance mechanisms when thermal refugia are available (e.g. behavioural thermoregulation). An increased need for avoidance behaviour could limit the accessibility of key habit for foraging and spawning which occurs in late summer in this region (Dubos et al., 2024).

Hidden decay of live trees in a tropical rain forest - Gregory S. Gilbert; Brant C. Faircloth; Travis C. Glenn; Javier O. Ballesteros; César A. Barrios‐Rodríguez; Ernesto Bonadies; Marjorie L. Cedeño‐Sánchez; Nohely J. Fossatti‐Caballero; José Moisés Pérez‐Suñiga; Mariam M. Trejos‐Rodríguez; Stephen P. Hubbell (Ecology, 2025)
The trunks of forest trees store massive amounts of carbon, but fungi actively and invisibly decay wood inside even seemingly healthy trees. Wood‐decay fungi are responsible for the loss of stored carbon in living trees, and they make trees susceptible to snapping and uprooting in storms. We used sonic tomography to measure the prevalence and severity of decay in 1744 live trees (≥20 cm diameter) of 171 species on the 50‐ha Forest Dynamics Plot on Barro Colorado Island, Panama. A median of 20% decay. Twenty percent of the combined basal area showed decay, representing a loss of approximately 1% of aboveground biomass. Larger trees more often showed internal decay, with one quarter of trees showing decay before reaching canopy height. Decay severity varied by species; 23% of species showed

Trace element distributions among Cu-(Fe)-sulfides from the Olympic Dam Cu-U-Au-Ag deposit, South Australia - Samuel A. King; Nigel J. Cook; Cristiana L. Ciobanu; Kathy Ehrig; Sarah Gilbert; Benjamin Wade; Yuri T. Campo Rodriguez (Mineralium Deposita, 2025)

Migratory Arctic char ( Salvelinus alpinus ) as a prey pulse for Arctic marine predators - Matthew J. H. Gilbert; Les N. Harris; Alexander L. Vail; Kristin L. Laidre; Mark L. Mallory; David J. Yurkowski (Ecology, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Coupled Lu-Hf and U-Pb apatite geochronology of Jatobá orebody supports ∼ 2.5 Ga metamorphism in deep shear zones from southern Copper Belt, Carajás Domain, Brazil - Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin Wade; Nigel J. Cook; Maria Emilia Schutesky; Kathy Ehrig (Precambrian Research, 2025)

Monazite, lanthanide-rich glasses, and other trace elements in copper smelter slags: constraints on critical metal behaviour in Si-Fe-rich melts - Hassan Gezzaz; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Ashley Slattery; Benjamin Wade; Sarah Gilbert; Yuri T. Campo Rodriguez (Mineralogy and Petrology, 2025)
Furnace slags are potential new sources of critical metals. We undertook a micron- to nanoscale study that addresses speciation, distribution and associations of phases in air-cooled flash furnace (FF, oxidised) and electric furnace (EF, reduced) slags from the Olympic Dam mining-smelting-refinery operation. Results enable understanding of the behaviour and partitioning of critical metals between melt and cooling crystalline phases in a controlled smelter environment that mimics Fe-Si-rich systems in Nature. Melts at ~ 1300 °C result in slags that differ in the relative proportions of component phases. Both FF and EF slags comprise major magnetite and two, compositionally distinct Si-Fe-rich glasses (glass-1 and -2); fayalite is a main component of EF slag. Glass-1 is rich in REE + Y (4.5–5.4 wt%, Ce 2 O 3 + La 2 O 3 ) and contains dendritic monazite-(Ce). Glass-2 (~ 70 wt% SiO 2 ) contains < 1 wt% Ce 2 O 3 + La 2 O 3 . The EF slag reaction sequence is: magnetite $$→$$ → fayalite + glass-1 $$→$$ → monazite $$→$$ → glass-2. Immiscibility of REE-rich liquid from Si-Fe-rich melt is inferred from amorphous ‘monazite-like’ droplets. Chondrite-normalised fractionation patterns are defined by downwards-sloping LREE segments in both glasses. Partition coefficients are calculated for magnetite and fayalite relative to glasses. D REY for HREE exceeds those for LREE in all phases and fayalite has an order of magnetite higher D HREE than co-existing EF magnetite. Applying lattice strain models to experimental values show excellent fits for D HREE-model trends, even if lattice strain is not the sole factor controlling partitioning. Melt polymerisation, variable/unpredictable oxidation states, and constraints from specific crystallographic sites, also impact on observed trends. This study provides clues to element behaviour in metallurgical plants that can assist potential utilization of copper smelter slags to meet the demand for REE and other contained critical metals.

Effects of temperature and nutrient load on the interaction of Vibrio parahaemolyticus and plastic pollution in the marine environment - Kara J. Wiggin; Ryan K. Chung; Jack A. Gilbert; Sarah M. Allard (Marine Pollution Bulletin, 2025)

PBPK Modeling to Support Bioavailability and Bioequivalence Assessment in Pediatric Populations - Fang Wu; Eleftheria Tsakalozou; Gilbert J. Burckart; Rebeka Žakelj; Lu Gaohua; Kazuko Sagawa; Viera Lukacova; Siva Vaithiyalingam; Jianghong Fan; Nikoletta Fotaki; Nikunjkumar Patel; Lanyan Fang (Pharmaceutical Research, 2025)
This report summarizes the proceedings for Session 3 of the one-day public workshop entitled “Advances in PBPK Modeling and its Regulatory Utility for Oral Drug Product Development” a jointly sponsored workshop by U.S. Food and Drug Administration (FDA) and the Center for Research on Complex Generics (CRCG) on October 12, 2023. The theme of this session was the application and relevant considerations for PBPK modeling in supporting bioavailability (BA) and BE assessment in pediatric populations. The takeaway message from this session was that PBPK modeling can support relative BA and BE assessment in pediatrics since such studies are generally performed in adults or healthy subjects. PBPK absorption modeling can incorporate characteristics of the drug substance and formulation as well as pediatric physiology to assess the potential differences in absorption of different formulations in pediatrics for new and generic drugs. It is necessary to consider the totality of data and use all available evidence integrated into a mechanistic PBPK model to support decision-making. Global research efforts are needed to bridge critical data gaps.

Temporal Loss of Genome‐Wide and Immunogenetic Diversity in a Near‐Extinct Parrot - Luke W. Silver; Katherine A. Farquharson; Emma Peel; M. Thomas P. Gilbert; Katherine Belov; Hernán E. Morales; Carolyn J. Hogg (Molecular Ecology, 2025)
Loss of genetic diversity threatens a species' adaptive potential and long‐term resilience. Predicted to be extinct by 2038, the orange‐bellied parrot ( Neophema chrysogaster ) is a critically endangered migratory bird threatened by numerous viral, bacterial and fungal diseases. The species has undergone multiple population crashes, reaching a low of three wild‐born females and 13 males in 2016, and is now represented by only a single wild population and individuals in the captive breeding program. Here we used our high‐quality long‐read reference genome, and contemporary ( N = 19) and historical ( N = 16) resequenced genomes from as early as 1829, to track the long‐term genomic erosion and immunogenetic diversity decline in this species. 62% of genomic diversity was lost between historical (mean autosomal heterozygosity = 0.00149 ± 0.000699 SD) and contemporary (0.00057 ± 0.000026) parrots. A greater number and length of runs of homozygosity in contemporary samples were also observed. A temporal reduction in the number of alleles at Toll‐like receptor genes was found (historical average alleles = 5.78 ± 2.73; contemporary = 3.89 ± 2.10), potentially exacerbating disease susceptibility in the contemporary population. Of particular concern is the new threat of avian influenza strain (HPAI) to Australia. We discuss the conservation implications of our findings and propose that hybridisation and synthetic biology may be required to address the catastrophic loss of genetic diversity that has occurred in this species in order to prevent extinction.

The potential of oviduct tags and fine‐scale acoustic telemetry to reveal the timing and location of spawning in Arctic salmonids ( Salvelinus spp.) - Véronique Dubos; Les N. Harris; Richard Ekpakohak; Brendan K. Malley; Matthew J. H. Gilbert; Nathan B. Furey; Jean‐Sébastien Moore (Journal of Fish Biology, 2025)
Identifying and characterizing spawning locations are paramount for the protection of critical fish habitats but can be challenging, particularly in remote locations. Using the underexplored oviduct‐tagging technique, we aimed to identify the timing and location of spawning for wild Arctic char ( Salvelinus alpinus ) and lake trout ( Salvelinus namaycush ) in two high‐Arctic lakes in Nunavut. Specifically, Innovasea V7 acoustic telemetry transmitters were inserted into the oviducts of 13 Arctic char and 4 lake trout, and the timing and location of tag expulsion were determined using a fine‐scale positioning system. Twenty Arctic char and 20 lake trout were also tagged with abdominal V16 transmitters, and 10 of them were paired with the oviduct tags, to further study the behavior of individual fish during the spawning season. Oviduct tags from four Arctic char and one lake trout could be used to assess the timing and location of spawning. Spawning anadromous Arctic char drastically reduced their activity and remained proximate to their presumed spawning location immediately before and for months after spawning. In contrast, a non‐anadromous (i.e., freshwater resident) Arctic char and a lake trout showed little to no reduction in activity around presumed spawning events. Because of the highlighted sedentary behavior of inferred spawning anadromous Arctic char implanted with both abdominal and oviduct tags, we could also infer potential spawning based on the behavior of individuals equipped only with abdominal tags. Spawning areas identified via telemetry also aligned well with Inuit knowledge of those lakes. This is the first field study to use acoustic oviduct and abdominal tags coupled with a fine‐scale positioning system. Despite a limited success rate of ejection, the study reveals the strong potential of the method to study spawning habitat and timing, particularly in remote areas.

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Mindful Eating and Diet Quality Among US Adults With Lower Incomes - Nour M. Hammad; Melissa J. Slotnick; Teresa T. Fung; Diane Gilbert-Diamond; Lilian W.Y. Cheung; Cindy W. Leung (Journal of the Academy of Nutrition and Dietetics, 2025)

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Additional analyses of stem catarrhine and hominoid dental morphology support Kapi ramnagarensis as a stem hylobatid - Christopher C. Gilbert; Alejandra Ortiz; Kelsey D. Pugh; Christopher J. Campisano; Biren A. Patel; Ningthoujam Premjit Singh; John G. Fleagle; Rajeev Patnaik (Journal of Human Evolution, 2025)

Using PeopleHour for occupant-centric office building performance assessment - Gulai Shen; John J. Gilbert; Ali Mehmani (Building and Environment, 2025)

Host Species–Microbiome Interactions Contribute to Sphagnum Moss Growth Acclimation to Warming - Tatjana Živković; Alyssa A. Carrell; Gustaf Granath; A. Jonathan Shaw; Dale A. Pelletier; Christopher W. Schadt; Dawn M. Klingeman; Mats B. Nilsson; Manuel Helbig; Denis Warshan; Ingeborg J. Klarenberg; Daniel Gilbert; et al. (Global Change Biology, 2025)
Sphagnum moss is the dominant plant genus in northern peatlands responsible for long‐term carbon accumulation. Sphagnum hosts diverse microbial communities (microbiomes), and its phytobiome (plant host + constituent microbiome + environment) plays a key role in nutrient acquisition along with carbon cycling. Climate change can modify the Sphagnum ‐associated microbiome, resulting in enhanced host growth and thermal acclimation as previously shown in warming experiments. However, the extent of microbiome benefits to the host and the influence of host–microbe specificity on Sphagnum thermal acclimation remain unclear. Here, we extracted Sphagnum microbiomes from five donor species of four peatland warming experiments across a latitudinal gradient and applied those microbiomes to three germ‐free Sphagnum species grown across a range of temperatures in the laboratory. Using this experimental system, we test if Sphagnum 's growth response to warming depends on the donor and/or recipient host species, and we determine how the microbiome's growth conditions in the field affect Sphagnum host growth across a range of temperatures in the laboratory. After 4 weeks, we found that the highest growth rate of recipient Sphagnum was observed in treatments of matched host–microbiome pairs, with rates approximately 50% and 250% higher in comparison to maximum growth rates of non‐matched host–microbiome pairs and germ‐free Sphagnum , respectively. We also found that the maximum growth rate of host–microbiome pairs was reached when treatment temperatures were close to the microbiome's native temperatures. Our study shows that Sphagnum 's growth acclimation to temperature is partially controlled by its constituent microbiome. Strong Sphagnum host–microbiome species specificity indicates the existence of underlying, unknown physiological mechanisms that may drive Sphagnum 's ability to acclimatize to elevated temperatures. Together with rapid acclimation of the microbiome to warming, these specific microbiome–plant associations have the potential to enhance peatland resilience in the face of climate change.

Mean plant toxicity modulates the effects of plant defense variability - Vincent S. Pan; Kadeem J. Gilbert; William C. Wetzel (Ecology, 2025)
Plant trait variation is thought to suppress herbivore performance, but experiments typically manipulate only a single mean level of the trait. We manipulated the mean and variation of the concentration of a plant toxin in a model plant–herbivore system across three field and greenhouse experiments. Plants with leaves painted with a higher mean toxin concentration exhibited increased fitness and resistance to herbivores; however, at high mean concentrations, variation reduced the defensive effect, while at lower mean concentrations, variation enhanced it. This reversal aligns with models that include herbivore food selectivity, but our simulations revealed that the benefits of food selectivity for herbivores were minimal. Instead, nonlinear averaging and physiological tracking effects likely drove patterns in plant fitness and resistance to herbivores. We suggest that high defense variation in plants may be a widespread defensive phenotype, but for well‐defended plants, variation may inadvertently promote herbivore niche expansion.

Mineralogy, mineral chemistry, and genesis of Cu-Ni-As-rich ores at Lisheen, Ireland - Max Frenzel; Markus Röhner; Nigel J. Cook; Sarah Gilbert; Cristiana L. Ciobanu; John F. Güven (Mineralium Deposita, 2025)
The Irish Orefield is characterised by the presence of both Zn-Pb- and Cu-Ni-As-rich deposits, prospects, and orebodies in similar structural and stratigraphic positions. However, the genetic relationships between these mineralisation types are still debated. In this article, we present new mineralogical, paragenetic, and mineral-chemical observations from the Cu-Ni-As-rich ores at the classic Lisheen deposit, County Tipperary. These observations indicate the intimate association and cogenetic nature of these ores with the more abundant Zn-Pb-rich mineralisation. Specifically, both mineralisation types appear to have formed at the same time, under similar physicochemical conditions, and from the same ore fluids. In addition, both types of mineralisation contain elevated Ge contents. The cogenetic nature of the two mineralisation types, the relative absence of Cu-Ni-As-rich ores from most of the larger Irish-type Zn-Pb deposits compared to expectations derived from probable ore fluid compositions, and finally, the known geological characteristics of larger Cu-Ni-As-rich ore bodies, like Gortdrum, indicate that significant Cu-Ni-As-rich mineralisation could be present at lower stratigraphic levels across the Irish Orefield. Areas with extensive known Zn-Pb mineralisation are expected to be particularly prospective for such ores, which may occur at stratigraphic levels as deep as the Old Red Sandstone. This may have additional implications beyond Ireland, and could point to the potential for undiscovered Cu-rich ores in low-temperature carbonate-hosted Zn-Pb districts elsewhere.

Why Is It Too Cold? Towards a Mechanistic Understanding of Cold‐Water Pollution Effects on Recruitment of an Imperiled Warmwater Fish - Eliza I. Gilbert; Tracy A. Diver; Steven M. Mussmann; Melody J. Saltzgiver; William K. Knight; Scott L. Durst; Michael A. Farrington; Stephani L. Clark Barkalow; Michael Tobler; Nathan R. Franssen (Molecular Ecology, 2025)
Environmental temperature shapes the ontogeny of ectotherms by influencing rates of growth and development which can be key determinants of survival. Whereas the escalating impacts of water management on freshwater ecosystems is well documented, the effects of cold‐water releases from dams—which can alter downstream temperatures—remains relatively underexplored but may present novel challenges to endemic ectotherms. Specifically, little is known about how thermal depressions reshape phenotypic and genetic patterns during larval metamorphosis for fishes that evolved in warmwater systems. We assessed the effects of thermal shifts on larval ontogeny of the endangered razorback sucker ( Xyrauchen texanus ), which evolved in the warm waters of the Colorado River Basin, USA. We hypothesised that development is more sensitive to cold‐water influences than growth and that temperature would influence patterns in gene expression related to development. Our results supported these hypotheses and showed that both wild and laboratory‐reared larvae in slightly cooler temperatures exhibited delayed development, but similar growth compared to larvae reared in warmer conditions. These findings suggest growth and development in early ectotherm life stages can be decoupled, which follows patterns more like the temperature‐size rule than allometric scaling of development by size. We also observed transcriptional differences related to genes associated with stress responses and development in our laboratory‐reared fish; here, gene expression of fish from the coldest conditions at the end of the experiment was more similar to fish reared in warmer temperatures at the midpoint. Our findings suggest that modest temperature reductions can delay ontogeny and alter the transcriptional landscape while not necessarily limiting growth. This finding highlights the need for conservation practitioners to consider cascading impacts that even small temperature reductions can cause in riverine ecosystems.

Invasive Buffelgrass, Cenchrus ciliaris , Balances Opportunistic Acquisition of Foliar fungi With Host and Environmental Filtering in Its Introduced Range - Elizabeth A. Bowman; Christine V. Hawkes; Nathan Jones; Robert M. Plowes; Dino J. Martins; Lawrence E. Gilbert (Molecular Ecology, 2025)
Plants host diverse assemblages of fungi on their foliar tissues, both in internal compartments and on exterior surfaces. When plant distributions shift, they can move with their fungal associates (i.e., co‐introduction) or acquire new associates present in the novel environment (host‐jumping). The fungal communities that plants acquire influence a plant's ability to establish and spread in this new environment. Here, we aimed to assess whether invasive C. ciliaris hosts similar groups of fungi in its native and introduced ranges and to evaluate community overlap of fungi associated with foliar tissue of C. ciliaris and native and non‐native plants within the introduced range. In the introduced range, the majority of OTUs associated with C. ciliaris were not found in its native range, although 3.2% of OTUs were common to both ranges. Of these shared OTU, 77.6% were found on co‐occurring natives and non‐natives in the introduced range, whereas 22.4% were unique to C. ciliaris indicating a possible co‐introduction. Fungal communities within the introduced range contained a higher proportion of generalist symbionts and increased heterogeneity of foliar communities than in its native range. Within the introduced range, host phylogenetic distance explained more variation than native status. Our findings provide evidence that non‐natives acquire fungi opportunistically from their environment, although host and environmental filtering is present suggesting that successful invasive plants may be able to limit the effect of poor symbionts and select for better ones. Future experimental work will be needed to confirm the occurrence of host selection and identify its mechanisms.

Large Differences in Herbivore Performance Emerge From Simple Herbivore Behaviours and Fine‐Scale Spatial Heterogeneity in Phytochemistry - Vincent S. Pan; Enakshi Ghosh; Paul J. Ode; William C. Wetzel; Kadeem J. Gilbert; Ian S. Pearse (Ecology Letters, 2025)
Patterns of phytochemistry localisation in plant tissues are diverse within and across leaves. These spatial heterogeneities are important to the fitness of herbivores, but their effects on herbivore foraging and dietary experience remain elusive. We manipulated the spatial variance and clusteredness of a plant toxin in a synthetic diet landscape on which individual caterpillars fed. We monitored caterpillars with cameras across most of their larval development. Caterpillars that fed on diets with a lower spatial variance and more clustered arrangement of toxins had overall worse performance, mostly because those caterpillars ate less, moved more, ingested more toxin, or failed to physiologically acclimate. Using empirically parameterised individual‐based models, we found that differences in movement away from, not towards, less toxic food drove a body size‐dependent effect of clusteredness. Hence, the spatial pattern of phytochemicals itself, beyond mean concentration, can have important consequences for herbivores through complex interactions with herbivore foraging.

Real-time in vivo confocal laser endomicroscopic imaging of equine endometrium: Preliminary observations and feasibility study - K. Gallacher; L. Woolford; L.C. Santos; P.B.S. Serpa; J. Len; R.O. Gilbert; K.L. Kind (The Veterinary Journal, 2024)

Vaccination of endangered wildlife as a conservation tool: Hindsights and new horizons in the pandemic era - Frances M.D. Gulland; Michelle Barbieri; Sarah Cleaveland; Martin Gilbert; Ailsa J. Hall; Tonie E. Rocke (Biological Conservation, 2024)

Computing optimal drug dosing regarding efficacy and safety: the enhanced OptiDose method in NONMEM - Freya Bachmann; Gilbert Koch; Robert J. Bauer; Britta Steffens; Gabor Szinnai; Marc Pfister; Johannes Schropp (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Recently, an optimal dosing algorithm (OptiDose) was developed to compute the optimal drug doses for any pharmacometrics model for a given dosing scenario. In the present work, we enhance the OptiDose concept to compute optimal drug dosing with respect to both efficacy and safety targets. Usually, these are not of equal importance, but one is a top priority, that needs to be satisfied, whereas the other is a secondary target and should be achieved as good as possible without failing the top priority target. Mathematically, this leads to state-constrained optimal control problems. In this paper, we elaborate how to set up such problems and transform them into classical unconstrained optimal control problems which can be solved in NONMEM. Three different optimal dosing tasks illustrate the impact of the proposed enhanced OptiDose method.

Potential for large losses of carbon from non-native conifer plantations on deep peat over decadal timescales - Thomas J. Sloan; Joshua Ratcliffe; Russell Anderson; W. Roland Gehrels; Peter Gilbert; Dmitri Mauquoy; Anthony J. Newton; Richard J. Payne; Justyna Serafin; Roxane Andersen (Science of The Total Environment, 2024)

The subreach effect: Multi-scale analysis reveals climate and irrigation infrastructure effects on flow intermittency in a regulated desert river - Eliza I. Gilbert; Thomas F. Turner; Melanie E. Moses; Alex J. Webster (Journal of Hydrology, 2024)

The role of annealing and grain boundary controls on the mechanical properties of limestones and marbles - Rui Zhang; Paul A. Bosomworth; Juliane Weber; Jan Ilavsky; Si Athena Chen; Alexis Flores-Betancourt; Elliot Paul Gilbert; Jitendra Mata; Mark L. Rivers; Peter J. Eng; Lawrence M. Anovitz (International Journal of Rock Mechanics and Mining Sciences, 2024)

Using zircon and apatite chemistry to fingerprint porphyry Cu – Mo ± Au mineralization in the Delamerian Orogen, South Australia - Wei Hong; Adrian Fabris; Sarah Gilbert; Benjamin P. Wade; Alan S. Collins; Tom Wise; Anthony J. Reid (Mineralium Deposita, 2024)
To evaluate the fertility of porphyry mineralization in the Delamerian Orogen (South Australia), zircon and apatite from four prospects, including Anabama Hill, Netley Hill, Bendigo, and Colebatch, have been analyzed by LA-ICP-MS and electron microprobe. The zircon is characterized by heavy REEs enrichment relative to light REEs, high (Ce/Nd) N (1.3–45), and weak to moderate negative Eu/Eu* (0.2–0.78). The apatite has right-sloped REE patterns with variably negative to positive Eu anomalies. Low Mg (< 670 ppm) and Sr/Y ratios (< 5) in apatite likely illustrate fractional crystallization trends for the granitic melts in shallow crust. The Yb/Gb and Eu/Eu* in zircon reveal that intrusions at Anabama Hill, Netley Hill, and Bendigo underwent fractional crystallization controlled by amphibole (< 50–60%), garnet (< 15%), apatite (< 0.6%), and/or titanite (< 0.3%). These stocks have average f O 2 values reported relative to fayalite-magnetite-quartz buffer (ΔFMQ), from 0.7 ± 0.9 to 2.1 ± 0.4, ascribed to prolonged magmatic evolution or sulfur degassing during post-subduction processes. Our data imply that both Anabama and Bendigo complexes experienced prevalent (garnet-) amphibole crystallization from hydrous melts that have moderately high oxidation (ΔFMQ + 1 to + 3) and elevated sulfur-chlorine components (Anabama, 37 ± 9 to 134 ± 83 ppm S and 0.30 ± 0.24 to 0.64 ± 0.89 wt% Cl; Bendigo, 281 ± 178 to 909 ± 474 ppm S and 0.45 ± 0.47 to 3.01 ± 1.54 wt% Cl). These are crucial ingredients to form porphyry Cu–Mo ± Au ores with economic significance, which provides encouragement for mineral exploration in this orogen.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Comparison of two carbonaceous supported Fe-rich adsorbents for arsenate removal: A functionalisation and mechanistic study with applicability to groundwater treatment - Sabolc Pap; Maja Turk Sekulic; Hai Nguyen Tran; Huan-Ping Chao; Peter J. Gilbert; Stuart W. Gibb; Mark A. Taggart (Chemosphere, 2024)

A century of statistical Ecology - Neil A. Gilbert; Bruna R. Amaral; Olivia M. Smith; Peter J. Williams; Sydney Ceyzyk; Samuel Ayebare; Kayla L. Davis; Wendy Leuenberger; Jeffrey W. Doser; Elise F. Zipkin (Ecology, 2024)
As data and computing power have surged in recent decades, statistical modeling has become an important tool for understanding ecological patterns and processes. Statistical modeling in ecology faces two major challenges. First, ecological data may not conform to traditional methods, and second, professional ecologists often do not receive extensive statistical training. In response to these challenges, the journal Ecology has published many innovative statistical ecology papers that introduced novel modeling methods and provided accessible guides to statistical best practices. In this paper, we reflect on Ecology 's history and its role in the emergence of the subdiscipline of statistical ecology, which we define as the study of ecological systems using mathematical equations, probability, and empirical data. We showcase 36 influential statistical ecology papers that have been published in Ecology over the last century and, in so doing, comment on the evolution of the field. As data and computing power continue to increase, we anticipate continued growth in statistical ecology to tackle complex analyses and an expanding role for Ecology to publish innovative and influential papers, advancing the discipline and guiding practicing ecologists.

Trace element impurities in anode copper from Olympic Dam, South Australia - Nigel J. Cook; Kathy Ehrig; Cristiana L. Ciobanu; Sarah E. Gilbert; Hassan Gezzaz (Minerals Engineering, 2024)

Evaluation of contingency actions to control the spread of raccoon rabies in Ohio and Virginia - Amy J. Davis; Richard B. Chipman; Kathleen M. Nelson; Betsy S. Haley; Jordona D. Kirby; Xiaoyue Ma; Ryan M. Wallace; Amy T. Gilbert (Preventive Veterinary Medicine, 2024)

Post-exercise management of exertional hyperthermia in dogs participating in dog sport (canicross) events in the UK - Anne J. Carter; Emily J. Hall; Jude Bradbury; Sian Beard; Sophie Gilbert; Dominic Barfield; Dan G. O'Neill (Journal of Thermal Biology, 2024)

Exposure to Nickel–Cadmium Contamination of Drinking Water Culminates in Liver Cirrhosis, Renal Azotemia, and Metabolic Stress in Rats - Augustine Apiamu; Oghenetega J. Avwioroko; Uduenevwo F. Evuen; Helen E. Kadiri; Enyohwo D. Kpomah; Akpovwehwee A. Anigboro; Gilbert Ugbebor; Samuel O. Asagba (Biological Trace Element Research, 2024)

Development of a culturally targeted chatbot to inform living kidney donor candidates of African ancestry about APOL1 genetic testing: a mixed methods study - Elisa J. Gordon; Jessica Gacki-Smith; Matthew J. Gooden; Preeya Waite; Rochell Yacat; Zenab R. Abubakari; Debra Duquette; Akansha Agrawal; John Friedewald; Sarah K. Savage; Matthew Cooper; Alexander Gilbert; et al. (Journal of Community Genetics, 2024)
Clinical chatbots are increasingly used to help integrate genetic testing into clinical contexts, but no chatbot exists for A polipoprotein L1 ( APOL1 ) genetic testing of living kidney donor (LKD) candidates of African ancestry. Our study aimed to culturally adapt and assess perceptions of the Gia® chatbot to help integrate APOL1 testing into LKD evaluation. Ten focus groups and post-focus group surveys were conducted with 54 LKDs, community members, and kidney transplant recipients of African ancestry. Data were analyzed through thematic analysis and descriptive statistics. Key themes about making Gia culturally targeted included ensuring: (1) transparency by providing Black LKDs’ testimonials, explaining patient privacy and confidentiality protections, and explaining how genetic testing can help LKD evaluation; (2) content is informative by educating Black LKDs about APOL1 testing instead of aiming to convince them to undergo testing, presenting statistics, and describing how genetic discrimination is legally prevented; and (3) content avoids stigma about living donation in the Black community. Most agreed Gia was neutral and unbiased (82%), trustworthy (82%), and words, phrases, and expressions were familiar to the intended audience (85%). Our culturally adapted APOL1 Gia chatbot was well regarded. Future research should assess how this chatbot could supplement provider discussion prior to genetic testing to scale APOL1 counseling and testing for LKD candidate clinical evaluation.

Development of alginate beads for precise environmental release applications: A design of experiment based approach and analysis - P.U. Ashvin Iresh Fernando; Alan J. Kennedy; Kaytee Pokrzywinski; Johanna Jernberg; Travis Thornell; Garrett George; Gilbert K. Kosgei; Yanfei Wang; Kathryn J. Coyne (Journal of Environmental Management, 2024)

Stream ecosystem puzzle: understanding how water column and sediment variables shape macroinvertebrate patterns in some Afrotropical streams - Simon Action; Francis O. Arimoro; Fulbert A. G. J. Assie; Diana Nantege; Gilbert Ndatimana; Unique N. Keke (Environmental Monitoring and Assessment, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Fish shrinking, energy balance and climate change - Quentin Queiros; David J. McKenzie; Gilbert Dutto; Shaun Killen; Claire Saraux; Quentin Schull (Science of The Total Environment, 2024)

Implications for metallogenic evolution of the giant Zhenyuan gold deposit (Yunnan, SW China) from textures and geochemical compositions of pyrite - Huichao Zhang; Nigel J. Cook; Hongrui Zhang; Zengqian Hou; Peng Chai; Wei Li; Sarah Gilbert (Contributions to Mineralogy and Petrology, 2024)

Farm level bio-economic modelling of aquatic animal disease and health interventions - E.J. Peeler; R. Caballero-Celli; C.E.S. Davila; A.C. Canales Gomez; W. Gilbert; M. Gómez-Sánchez; Huntington; V.T. Phan; J. Rushton; R.S. Schrijver; A. Kennerley (Preventive Veterinary Medicine, 2023)

Expert-driven play Fairway Analysis applied to the Azufral Volcano Geothermal Area in southwestern Colombia - Emmanuel Olvera-García; Bridget F. Ayling; Jesús B. Rueda-Gutiérrez; Anieri M. Morales Rivera; Gilbert F. Rodríguez-Rodríguez; Jaison Malo; Jefferson Sánchez; Yeimy Rodríguez-Molina; Yerson Pardo; Yenny P. Casallas-Veloza; J. Camilo Matiz-León; Gina Rodríguez-Ospina; et al. (Geothermics, 2023)

Periconceptional and Prenatal Exposure to Metals and Extracellular Vesicle and Particle miRNAs in Human Milk: A Pilot Study - Caitlin G. Howe; David A. Armstrong; Meghan E. Muse; Diane Gilbert-Diamond; Jiang Gui; Anne G. Hoen; Thomas J. Palys; Roxanna L. Barnaby; Bruce A. Stanton; Brian P. Jackson; Brock C. Christensen; Margaret R. Karagas (Exposure and Health, 2023)

Ericoid shrub encroachment shifts aboveground–belowground linkages in three peatlands across Europe and Western Siberia - Alexandre Buttler; Luca Bragazza; Fatima Laggoun‐Défarge; Sebastien Gogo; Marie‐Laure Toussaint; Mariusz Lamentowicz; Bogdan H. Chojnicki; Michał Słowiński; Sandra Słowińska; Małgorzata Zielińska; Monika Reczuga; Jan Barabach; et al. (Global Change Biology, 2023)
In northern peatlands, reduction of Sphagnum dominance in favour of vascular vegetation is likely to influence biogeochemical processes. Such vegetation changes occur as the water table lowers and temperatures rise. To test which of these factors has a significant influence on peatland vegetation, we conducted a 3‐year manipulative field experiment in Linje mire (northern Poland). We manipulated the peatland water table level (wet, intermediate and dry; on average the depth of the water table was 17.4, 21.2 and 25.3 cm respectively), and we used open‐top chambers (OTCs) to create warmer conditions (on average increase of 1.2°C in OTC plots compared to control plots). Peat drying through water table lowering at this local scale had a larger effect than OTC warming treatment per see on Sphagnum mosses and vascular plants. In particular, ericoid shrubs increased with a lower water table level, while Sphagnum decreased. Microclimatic measurements at the plot scale indicated that both water‐level and temperature, represented by heating degree days (HDDs), can have significant effects on the vegetation. In a large‐scale complementary vegetation gradient survey replicated in three peatlands positioned along a transitional oceanic–continental and temperate–boreal (subarctic) gradient (France–Poland–Western Siberia), an increase in ericoid shrubs was marked by an increase in phenols in peat pore water, resulting from higher phenol concentrations in vascular plant biomass. Our results suggest a shift in functioning from a mineral‐N‐driven to a fungi‐mediated organic‐N nutrient acquisition with shrub encroachment. Both ericoid shrub encroachment and higher mean annual temperature in the three sites triggered greater vascular plant biomass and consequently the dominance of decomposers (especially fungi), which led to a feeding community dominated by nematodes. This contributed to lower enzymatic multifunctionality. Our findings illustrate mechanisms by which plants influence ecosystem responses to climate change, through their effect on microbial trophic interactions.

Peptide-based pore formation and cell membrane deformation: European Biophysics Journal Prizes at EBSA 2023 - Robert J. C. Gilbert (European Biophysics Journal, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Positive responses of breeding waders to targeted conservation advice and habitat management used to enhance existing wader conservation initiatives in Northern Ireland - Christina L. Hunt; Kendrew Colhoun; Lucy R. Mason; Gillian Gilbert; Claire Barnett; Will J. Peach (Journal for Nature Conservation, 2023)

Associations between behavioral self-regulation and external food cue responsiveness (EFCR) in preschool-age children and evidence of modification by parenting style - Dabin Yeum; Diane Gilbert-Diamond; Travis D. Masterson; Delaina D. Carlson; Grace A. Ballarino; Reina K. Lansigan; Timothy J. Renier; Jennifer A. Emond (Appetite, 2023)

Organic carbon in British lowland ponds: estimating sediment stocks, possible practical benefits and significant unknowns - Michael J. Jeffries; Peter J. Gilbert; Scott Taylor; David A. Cooke; Michael E. Deary (Hydrobiologia, 2023)
Ponds are aquatic habitats defined by their small size. Although small they are found on every continent, they are disproportionately rich in aquatic biodiversity, benefit terrestrial wildlife and have important ecosystem function benefits. One of these benefits might be carbon sequestration, a possibility suggested by (1) their abundance, (2) the intensity of their biogeochemical activity. Whilst greenhouse gas fluxes from ponds have been monitored widely, quantifying the stocks of organic carbon buried in sediment is a gap in our knowledge. Here we summarise measures of organic carbon in pond sediments cores from a diverse range of lowland ponds in England. We estimate a general measure of 9.38 kg OC in a 1 m 2 × 20 cm block of pond sediment and scale this up to an overall estimate for Great Britain of 2.63 million tons of OC in pond sediment, with 95% CI of 1.41 to 3.84 million tons. The relationship between sediment carbon and gas fluxes remains a significant unknown.

Assessment of pixel-oriented k-NN machine learning algorithm performance for the interannual remote sensing monitoring of eelgrass beds at the mouth of the Romaine - P. Lemieux; C. Lalumière; N. Fugaru; J.-P. Gilbert; A. Tremblay (Environmental Monitoring and Assessment, 2023)
Eelgrass cover extent is among the most reliable indicators for measuring changes in coastal ecosystems. Eelgrass has colonized the mouth of the Romaine River and has become a part of environmental monitoring there since 2013. The presence of eelgrass in this area is an essential factor for the early detection of changes in the Romaine coastal ecosystem. This will act as a trigger for an appropriate environmental response to preserve ecosystem health. In this paper, a cost- and time-efficient workflow for such spatial monitoring is proposed using a pixel-oriented k-NN algorithm. It can then be applied to multiple modellers to efficiently map the eelgrass cover. Training data were collected to define key variables for segmentation and k-NN classification, providing greater edge detection for the presence of eelgrass. The study highlights that remote sensing and training data must be acquired under similar conditions, replicating methodologies for collecting data on the ground. Similar approaches must be used for the zonal statistic requirements of the monitoring area. This will allow a more accurate and reliable assessment of eelgrass beds over time. An overall accuracy of over 90% was achieved for eelgrass detection for each year of monitoring.

Multi-timescale dynamics of extreme river flood and storm surge interactions in relation with large-scale atmospheric circulation: Case of the Seine estuary - E.I. Turki; J. Deloffre; N. Lecoq; R. Gilbert; E.T. Mendoza; B. Laignel; E. Salameh; A.D. Gutierrez Barcelo; M. Fournier; N. Massei (Estuarine, Coastal and Shelf Science, 2023)

Integration of Biorelevant Pediatric Dissolution Methodology into PBPK Modeling to Predict In Vivo Performance and Bioequivalence of Generic Drugs in Pediatric Populations: a Carbamazepine Case Study - Gopal Pawar; Fang Wu; Liang Zhao; Lanyan Fang; Gilbert J. Burckart; Kairui Feng; Youssef M. Mousa; Abdullah Al Shoyaib; Marie-Christine Jones; Hannah K. Batchelor (The AAPS Journal, 2023)
This study investigated the impact of gastro-intestinal fluid volume and bile salt (BS) concentration on the dissolution of carbamazepine (CBZ) immediate release (IR) 100 mg tablets and to integrate these in vitro biorelevant dissolution profiles into physiologically based pharmacokinetic modelling (PBPK) in pediatric and adult populations to determine the biopredictive dissolution profile. Dissolution profiles of CBZ IR tablets (100 mg) were generated in 50–900 mL biorelevant adult fasted state simulated gastric and intestinal fluid (Ad-FaSSGF and Ad-FaSSIF), also in three alternative compositions of biorelevant pediatric FaSSGF and FaSSIF medias at 200 mL. This study found that CBZ dissolution was poorly sensitive to changes in the composition of the biorelevant media, where dissimilar dissolution (F2 = 46.2) was only observed when the BS concentration was changed from 3000 to 89 μM (Ad-FaSSIF vs Ped-FaSSIF 50% 14 BS). PBPK modeling demonstrated the most predictive dissolution volume and media composition to forecast the PK was 500 mL of Ad-FaSSGF/Ad-FaSSIF media for adults and 200 mL Ped-FaSSGF/FaSSIF media for pediatrics. A virtual bioequivalence simulation was conducted by using Ad-FaSSGF and/or Ad-FaSSIF 500 mL or Ped-FaSSGF and/or Ped-FaSSIF 200 mL dissolution data for CBZ 100 mg (reference and generic test) IR product. The CBZ PBPK models showed bioequivalence of the product. This study demonstrates that the integration of biorelevant dissolution data can predict the PK profile of a poorly soluble drug in both populations. Further work using more pediatric drug products is needed to verify biorelevant dissolution data to predict the in vivo performance in pediatrics. Graphical Abstract

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Electrocardiogram to Determine Mitral and Aortic Valve Opening and Closure - M. Rifqi Aufan; Zachary T. Jost; Neal J. Miller; Oleg F. Sharifov; Himanshu Gupta; Gilbert J. Perry; J. Michael Wells; Thomas S. Denney; Steven G. Lloyd (Cardiovascular Engineering and Technology, 2023)

Computing optimal drug dosing with OptiDose: implementation in NONMEM - Freya Bachmann; Gilbert Koch; Robert J. Bauer; Britta Steffens; Gabor Szinnai; Marc Pfister; Johannes Schropp (Journal of Pharmacokinetics and Pharmacodynamics, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Interspecific oral rabies vaccine bait competition in the Southeast United States - Wesley C. Dixon; Jacob E. Hill; Richard B. Chipman; Amy J. Davis; Amy T. Gilbert; James C. Beasley; Olin E. Rhodes; Guha Dharmarajan (Applied Animal Behaviour Science, 2023)

Effects of ants on riparian poplars: an ex situ experiment of biotic interaction - D. Corenblit; B. Corbara; R. Cereghino; A. Dejean; P. Duran; V. Garófano-Gómez; F. Gilbert; E. González-Sargas; F. Julien; L. Lambs; C. Mainguin; L. Mazal; et al. (Arthropod-Plant Interactions, 2023)

Hemicellulose-bacterial cellulose ribbon interactions affect the anisotropic mechanical behaviour of bacterial cellulose hydrogels - Si-Qian Chen; Patricia Lopez-Sanchez; Deirdre Mikkelsen; Marta Martinez-Sanz; Zhaofeng Li; Shuyan Zhang; Elliot P. Gilbert; Lin Li; Michael J. Gidley (Food Hydrocolloids, 2023)

Evaluation of phosphorus runoff from sandy soils under conservation tillage with surface broadcasted recovered phosphates - Clement D.D. Sohoulande; Ariel A. Szogi; Kenneth C. Stone; Gilbert C. Sigua; Jerry H. Martin; Paul D. Shumaker; Phil J. Bauer (Journal of Environmental Management, 2023)

Biodiversity patterns diverge along geographic temperature gradients - Charlie J. G. Loewen; Donald A. Jackson; Benjamin Gilbert (Global Change Biology, 2023)
Models applying space‐for‐time substitution, including those projecting ecological responses to climate change, generally assume an elevational and latitudinal equivalence that is rarely tested. However, a mismatch may lead to different capacities for providing climatic refuge to dispersing species. We compiled community data on zooplankton, ectothermic animals that form the consumer basis of most aquatic food webs, from over 1200 mountain lakes and ponds across western North America to assess biodiversity along geographic temperature gradients spanning nearly 3750 m elevation and 30° latitude. Species richness, phylogenetic relationships, and functional diversity all showed contrasting responses across gradients, with richness metrics plateauing at low elevations but exhibiting intermediate latitudinal maxima. The nonmonotonic/hump‐shaped diversity trends with latitude emerged from geographic interactions, including weaker latitudinal relationships at higher elevations (i.e. in alpine lakes) linked to different underlying drivers. Here, divergent patterns of phylogenetic and functional trait dispersion indicate shifting roles of environmental filters and limiting similarity in the assembly of communities with increasing elevation and latitude. We further tested whether gradients showed common responses to warmer temperatures and found that mean annual (but not seasonal) temperatures predicted elevational richness patterns but failed to capture consistent trends with latitude, meaning that predictions of how climate change will influence diversity also differ between gradients. Contrasting responses to elevation‐ and latitude‐driven warming suggest different limits on climatic refugia and likely greater barriers to northward range expansion.

Extinction dynamics: The interplay of species traits and the spatial scales of metapopulation declines - Emma J. Walker; Benjamin Gilbert (Ecology, 2023)
Global changes can lead to species declines and extinctions through their impacts on species habitats at two distinct spatial scales: habitat destruction, in which individual habitat patches are destroyed by land‐use change or natural disasters, and habitat degradation, in which larger scale changes, such as nitrogen deposition or climate change, lower mean population abundances across landscapes. We developed a theory showing that, even when these two forms of global change have an identical impact on a species' total amount of habitat, they have qualitatively different consequences for species dynamics and extinction. Using metapopulation theory and simulations, we found distinct impacts of these global changes characterized through several responses: the rate at which populations are lost from the remaining patches, extinction thresholds, and the duration of extinction debts. Habitat degradation causes a faster decline in species populations when habitat reduction is low, making it particularly detrimental for rare species. Habitat destruction has smaller impacts for low habitat reduction, but shows clear thresholds beyond which it surpasses degradation's negative impact; the location and steepness of the threshold depends on species dispersal, with poor dispersers having steeper thresholds. These results highlight the challenge of using population monitoring to assess the consequences of global changes and predict consequences of further change: extinction trajectories cannot be predicted due to thresholds (habitat destruction) and lagged dynamics that lead to extinction debts (habitat degradation). Our research clarifies why the impacts of one type of global change may poorly predict the impacts of the other and suggests general rules for predicting the long‐term impacts of global changes based on species traits.

Efficacy and Fate of Fluridone Applications for Control of Invasive Submersed Aquatic Vegetation in the Estuarine Environment of the Sacramento-San Joaquin Delta - Nick Rasmussen; J. Louise Conrad; Heather Green; Shruti Khanna; Hailey Wright; Krista Hoffmann; Jeffrey Caudill; Patricia Gilbert (Estuaries and Coasts, 2022)
Estuaries are ecologically and economically important ecosystems but are threatened by non-native invasive species, including many species of submersed aquatic vegetation (SAV). Herbicides are the primary tool used to control SAV, but most field evaluations of herbicides have been conducted in lentic systems. Therefore, managers working in estuaries must base their SAV control programs largely on findings from systems fundamentally different from their own. We conducted a study in the Sacramento-San Joaquin Delta to determine efficacy of the widely used herbicide fluridone in an estuarine ecosystem. The primary goal of SAV removal was restoration of open water habitat for endangered Hypomesus transpacificus (Delta Smelt). Over 18 months and multiple sets of multi-week fluridone applications, we monitored concentrations of fluridone and responses by SAV across pairs of treated and reference sites. Fluridone concentrations in the water were generally below the 2–5 parts per billion required for SAV control. Monitoring demonstrated that these low water concentrations were likely due to dissipation by tides, despite use of pelleted fluridone formulations marketed for flowing water environments. Fluridone did, however, accumulate in sediment at concentrations hundreds of times higher than those measured in the water. Nonetheless, we did not observe lasting reductions in SAV abundance or changes in SAV community composition. By demonstrating lack of efficacy of one of the few herbicides permitted for use in this estuary, this study highlights the need for development of SAV management tools tailored to the challenges of hydrologically complex environments like estuaries.

Food niches of planktonic rotifers: Diversification and implications - John J. Gilbert (Limnology and Oceanography, 2022)
The diverse diets of common planktonic rotifers are described in detail from field and laboratory observations and experiments. Also considered are methodological approaches, rotifer feeding mechanisms, and the availability in natural waters of less well‐known food items (detritus, picoplankton, protozoans). Despite much variation among and within rotifer genera, food niches of planktonic rotifers can be subdivided into four broad, overlapping categories defined by the predominant types and sizes of food ingested: (1) microphagous rotifers that eat fine detritus/organic aggregates, picoplankton, and 2–10 μ m nanoplankton; (2) polyphagous rotifers that eat the above items, larger nanoplankton, and small (20–50 μ m) microplankton; (3) macrophagous algivores that eat 5–50 μ m algae; and (4) macrophagous omnivores/predators that eat 5–250 μ m algae, protozoans, and metazoans. These diet‐based categories have ecological advantages over categories based on rotifer morphology or feeding mode. The information on diets assembled here is important for understanding: (1) the population dynamics of planktonic rotifers and their food organisms; (2) the position of rotifers in classical and microbial food webs; (3) the seasonality, spatial distribution, and species diversity of rotifers in plankton communities; and (4) food overlap, and thus potential resource competition, among planktonic protozoans, rotifers, and crustaceans.

Convergence of monosynaptic inputs from neurons in the brainstem and forebrain on parabrachial neurons that project to the paraventricular nucleus of the thalamus - Gilbert J. Kirouac; Sa Li; Shuanghong Li (Brain Structure and Function, 2022)
The paraventricular nucleus of the thalamus (PVT) projects to areas of the forebrain involved in regulating behavior. Homeostatic challenges and salient cues activate the PVT and evidence shows that the PVT regulates appetitive and aversive responses. The brainstem is a source of afferents to the PVT and the present study was done to determine if the lateral parabrachial nucleus (LPB) is a relay for inputs to the PVT. Retrograde tracing experiments with cholera toxin B (CTB) demonstrate that the LPB contains more PVT projecting neurons than other regions of the brainstem including the catecholamine cell groups. The hypothesis that the LPB is a relay for signals to the PVT was assessed using an intersectional monosynaptic rabies tracing approach. Sources of inputs to LPB included the reticular formation; periaqueductal gray (PAG); nucleus cuneiformis; and superior and inferior colliculi. Distinctive clusters of input cells to LPB-PVT projecting neurons were also found in the dorsolateral bed nucleus of the stria terminalis (BSTDL) and the lateral central nucleus of the amygdala (CeL). Anterograde viral tracing demonstrates that LPB-PVT neurons densely innervate all regions of the PVT in addition to providing collateral innervation to the preoptic area, lateral hypothalamus, zona incerta and PAG but not the BSTDL and CeL. The paper discusses the anatomical evidence that suggests that the PVT is part of a network of interconnected neurons involved in arousal, homeostasis, and the regulation of behavioral states with forebrain regions potentially providing descending modulation or gating of signals relayed from the LPB to the PVT.

Chromosomal inversions can limit adaptation to new environments - Marius Roesti; Kimberly J. Gilbert; Kieran Samuk (Molecular Ecology, 2022)
Chromosomal inversions are often thought to facilitate local adaptation and population divergence because they can link multiple adaptive alleles into non‐recombining genomic blocks. Selection should thus be more efficient in driving inversion‐linked adaptive alleles to high frequency in a population, particularly in the face of maladaptive gene flow. But what if ecological conditions and hence selection on inversion‐linked alleles change? Reduced recombination within inversions could then constrain the formation of optimal combinations of pre‐existing alleles under these new ecological conditions. Here, we outline this idea of inversions limiting adaptation and divergence when ecological conditions change across time or space. We reason and use simulations to illustrate that the benefit of inversions for local adaptation and divergence under one set of ecological conditions can come with a concomitant constraint for adaptation to novel sets of ecological conditions. This limitation of inversions to adaptation may contribute to the maintenance of polymorphism within species.

Legacies of invasive plant management: effects of leaching from glyphosate-treated and untreated plants on germination and early growth of native macrophytes - Verena Sesin; Joanna R. Freeland; Janice M. Gilbert; Kevin J. Stevens; Christina M. Davy (Biological Invasions, 2022)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece - Max Frenzel; Panagiotis Voudouris; Nigel J. Cook; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin P. Wade (Mineralium Deposita, 2022)
Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and f S 2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results from previous fluid-inclusion studies. Chalcopyrite chemistry also shows systematic variations over time, particularly for Cd, Co, Ge, In, Sn and Zn concentrations. Measurable pyrite was only found in association with early high-temperature mineralisation, and no clear trends could therefore be identified. We note, however, that As and Se contents in pyrite are consistent with formation temperatures estimated from co-existing sphalerite. Statistical analysis of the sphalerite data allowed us to identify the dominant geological controls on its trace-element content. The three investigated factors temperature, f S 2 , and sample location account for > 80% of the observed variance in Mn, Fe, Co, Ga, Ge, In, Sb and Hg concentrations, and > 60% of the observed variance in Cd and Sn concentrations. Only for Cu and Ag concentrations is the explained variance < 50%. A similarly detailed analysis was not possible for chalcopyrite and pyrite. Nevertheless, comparison of the results for all three investigated minerals indicates that there are some systematic variations across the deposit which may be explained by local differences in fluid composition.

Sorbents for treatment of hereditary hemochromatosis - Anna Wilson; Leslie Laguna; Lansten Yew; Kerry Kao; Kathryn Bauguess; Jiaying Wang; Sofia de la O; Grant Romme; William Gilbert; Ana Rita C. Morais; Jian Qian; Cory J. Berkland; et al. (Medicinal Chemistry Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Still time for action: genetic conservation of imperiled South Canadian River fishes, Arkansas River Shiner (Notropis girardi), Peppered Chub (Macrhybopsis tetranema) and Plains Minnow (Hybognathus placitus) - Megan J. Osborne; Joanna L. Hatt; Eliza I. Gilbert; Stephen R. Davenport (Conservation Genetics, 2021)

The dilemma of Guinea grass (Megathyrsus maximus): a valued pasture grass and a highly invasive species - Aaron C. Rhodes; Robert M. Plowes; John A. Goolsby; John F. Gaskin; Boaz Musyoka; Paul-André Calatayud; Massimo Cristofaro; Eric D. Grahmann; Dino J. Martins; Lawrence E. Gilbert (Biological Invasions, 2021)

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Predicting moisture content during maize nixtamalization using machine learning with NIR spectroscopy - Michael J. Burns; Jonathan S. Renk; David P. Eickholt; Amanda M. Gilbert; Travis J. Hattery; Mark Holmes; Nickolas Anderson; Amanda J. Waters; Sathya Kalambur; Sherry A. Flint-Garcia; Marna D. Yandeau-Nelson; George A. Annor; et al. (Theoretical and Applied Genetics, 2021)

Shrinking into the big city: influence of genetic and environmental factors on urban dragon lizard morphology and performance capacity - James Baxter-Gilbert; Julia L. Riley; Celine H. Frère; Martin J. Whiting (Urban Ecosystems, 2021)

Does a Trawl Ban Benefit Commercially Important Decapoda and Stomatopoda in Hong Kong? - Lily S. R. Tao; Gilbert C. S. Lui; Kingsley J. H. Wong; Tommy T. Y. Hui; Yanny K. Y. Mak; Ronia C.-t Sham; Jason K. C. Yau; William W. L. Cheung; Kenneth M. Y. Leung (Ecosystems, 2021)
Crustaceans were among the most valuable fishery resources in Hong Kong. However, the unrestricted and intensive use of different fishing gears, especially bottom trawling, has led to the depletion of commercially important crustaceans in Hong Kong since the 1980s. This study investigated whether commercial crustaceans recovered after the implementation of a permanent Hong Kong-wide trawl ban that began on December 31, 2012. Standardized field surveys were conducted using a commercial shrimp trawler at two sites in eastern and western waters of Hong Kong before (2004) and after the trawl ban (2013–2014 and 2015–2016) and two sites in southern waters after the trawl ban. Diversity, mean size, abundance, biomass and level of disturbance of commercial crustaceans from the three periods were investigated. The eastern waters exhibited an increased diversity of crustacean assemblages in Inner Tolo, and a higher abundance and biomass of crabs were detected in Outer Tolo after the trawl ban. Reduced disturbance, higher diversity in crustacean assemblages and greater abundance and biomass of predatory crabs were observed after the trawl ban in the outer estuary of western waters, and increased abundance and biomass of shrimp were detected in the inner estuary of western waters. No temporal or negative changes were detected in the southeast and southern waters of Lamma Island. The various responses of crustacean assemblages in Hong Kong waters revealed the critical role of complex interactions among multiple stresses, such as ongoing reclamation works, illegal trawling activities and increased fishing efforts using other (legal) fishing methods.

Extensive divergence of projections to the forebrain from neurons in the paraventricular nucleus of the thalamus - Sa Li; Xinwen Dong; Gilbert J. Kirouac (Brain Structure and Function, 2021)
Neurons in the paraventricular nucleus of the thalamus (PVT) respond to emotionally salient events and project densely to subcortical regions known to mediate adaptive behavioral responses. The areas of the forebrain most densely innervated by the PVT include striatal-like subcortical regions that consist of the shell of the nucleus accumbens (NAcSh), the dorsolateral region of the bed nucleus of the stria terminalis (BSTDL) and the lateral-capsular division of the central nucleus of the amygdala (CeL). A recent tracing experiment demonstrated that the PVT is composed of two intermixed populations of neurons that primarily project to either the dorsomedial (dmNAcSh) or ventromedial region of the NAcSh (vmNAcSh) with many of the vmNAcSh projecting neurons providing collateral innervation of the BSTDL and CeL. The present study used triple injections of the retrograde tracer cholera toxin B to provide a detailed map of the location of PVT neurons that provide collaterals to the vmNAcSh, BSTDL and CeL. These neurons were intermixed throughout the PVT and did not form uniquely localized subpopulations. An intersectional viral anterograde tracing approach was used to demonstrate that regardless of its presumed target of innervation (dmNAcSh, vmNAcSh, BSTDL, or CeL), most neurons in the PVT provide collateral innervation to a common set of forebrain regions. The paper shows that PVT-dmNAcSh projecting neurons provide the most divergent projection system and that these neurons express the immediate early gene product cFos following an aversive incident. We propose that the PVT may regulate a broad range of responses to physiological and psychological challenges by simultaneously influencing functionally diverse regions of the forebrain that include the cortex, striatal-like regions in the basal forebrain and a number of hypothalamic nuclei.

The virtual goniometer: demonstrating a new method for measuring angles on archaeological materials using fragmentary bone - Katrina Yezzi-Woodley; Jeff Calder; Peter J. Olver; Paige Cody; Thomas Huffstutler; Alexander Terwilliger; J. Anne Melton; Martha Tappen; Reed Coil; Gilbert Tostevin (Archaeological and Anthropological Sciences, 2021)

Leech blood‐meal invertebrate‐derived DNA reveals differences in Bornean mammal diversity across habitats - Rosie Drinkwater; Tommaso Jucker; Joshua H. T. Potter; Tom Swinfield; David A. Coomes; Eleanor M. Slade; M. Thomas P. Gilbert; Owen T. Lewis; Henry Bernard; Matthew J. Struebig; Elizabeth L. Clare; Stephen J. Rossiter (Molecular Ecology, 2021)
The application of metabarcoding to environmental and invertebrate‐derived DNA (eDNA and iDNA) is a new and increasingly applied method for monitoring biodiversity across a diverse range of habitats. This approach is particularly promising for sampling in the biodiverse humid tropics, where rapid land‐use change for agriculture means there is a growing need to understand the conservation value of the remaining mosaic and degraded landscapes. Here we use iDNA from blood‐feeding leeches ( Haemadipsa picta ) to assess differences in mammalian diversity across a gradient of forest degradation in Sabah, Malaysian Borneo. We screened 557 individual leeches for mammal DNA by targeting fragments of the 16S rRNA gene and detected 14 mammalian genera. We recorded lower mammal diversity in the most heavily degraded forest compared to higher quality twice logged forest. Although the accumulation curves of diversity estimates were comparable across these habitat types, diversity was higher in twice logged forest, with more taxa of conservation concern. In addition, our analysis revealed differences between the community recorded in the heavily logged forest and that of the twice logged forest. By revealing differences in mammal diversity across a human‐modified tropical landscape, our study demonstrates the value of iDNA as a noninvasive biomonitoring approach in conservation assessments.

3D Morphometric Analysis Reveals Similar Ecomorphs for Early Kangaroos (Macropodidae) and Fanged Kangaroos (Balbaridae) from the Riversleigh World Heritage Area, Australia - Kaylene Butler; Kenny J. Travouillon; Alistair R. Evans; Laura Murphy; Gilbert J. Price; Michael Archer; Suzanne J. Hand; Vera Weisbecker (Journal of Mammalian Evolution, 2021)

Using DNA to distinguish between faeces of Dugong dugon and Chelonia mydas: non-invasive sampling for IUCN-listed marine megafauna - S. J. Tol; M. Harrison; R. Groom; J. Gilbert; D. Blair; R. Coles; B. C. Congdon (Conservation Genetics Resources, 2021)

EXPRESSION OF CONCERN: InsectChange: a global database of temporal changes in insect and arachnid assemblages - Roel van Klink; Diana E. Bowler; Orr Comay; Michael M. Driessen; S. K. Morgan Ernest; Alessandro Gentile; Francis Gilbert; Konstantin B. Gongalsky; Jennifer Owen; Guy Pe'er; Israel Pe'er; Vincent H. Resh; et al. (Ecology, 2021)
Insects are the most ubiquitous and diverse group of eukaryotic organisms on Earth, forming a crucial link in terrestrial and freshwater food webs. They have recently become the subject of headlines because of observations of dramatic declines in some places. Although there are hundreds of long‐term insect monitoring programs, a global database for long‐term data on insect assemblages has so far remained unavailable. In order to facilitate synthetic analyses of insect abundance changes, we compiled a database of long‐term (≥10 yr) studies of assemblages of insects (many also including arachnids) in the terrestrial and freshwater realms. We searched the scientific literature and public repositories for data on insect and arachnid monitoring using standardized protocols over a time span of 10 yr or longer, with at least two sampling events. We focused on studies that presented or allowed calculation of total community abundance or biomass. We extracted data from tables, figures, and appendices, and, for data sets that provided raw data, we standardized trapping effort over space and time when necessary. For each site, we extracted provenance details (such as country, state, and continent) as well as information on protection status, land use, and climatic details from publicly available GIS sources. In all, the database contains 1,668 plot‐level time series sourced from 165 studies with samples collected between 1925 and 2018. Sixteen data sets provided here were previously unpublished. Studies were separated into those collected in the terrestrial realm (103 studies with a total of 1,053 plots) and those collected in the freshwater realm (62 studies with 615 plots). Most studies were from Europe (48%) and North America (29%), with 34% of the plots located in protected areas. The median monitoring time span was 19 yr, with 12 sampling years. The number of individuals was reported in 129 studies, the total biomass was reported in 13 studies, and both abundance and biomass were reported in 23 studies. This data set is published under a CC‐BY license, requiring attribution of the data source. Please cite this paper if the data are used in publications, and respect the licenses of the original sources when using (part of) their data as detailed in Metadata S1: Table 1.

Development of a Pediatric Relative Bioavailability/Bioequivalence Database and Identification of Putative Risk Factors Associated With Evaluation of Pediatric Oral Products - Gopal Pawar; Fang Wu; Liang Zhao; Lanyan Fang; Gilbert J. Burckart; Kairui Feng; Youssef M. Mousa; Franci Naumann; Hannah K. Batchelor (The AAPS Journal, 2021)
Generally, bioequivalence (BE) studies of drug products for pediatric patients are conducted in adults due to ethical reasons. Given the lack of direct BE assessment in pediatric populations, the aim of this work is to develop a database of BE and relative bioavailability (relative BA) studies conducted in pediatric populations and to enable the identification of risk factors associated with certain drug substances or products that may lead to failed BE or different pharmacokinetic (PK) parameters in relative BA studies in pediatrics. A literature search from 1965 to 2020 was conducted in PubMed, Cochrane Library, and Google Scholar to identify BE studies conducted in pediatric populations and relative BA studies conducted in pediatric populations. Overall, 79 studies covering 37 active pharmaceutical ingredients (APIs) were included in the database: 4 bioequivalence studies with data that passed BE evaluations; 2 studies showed bioinequivalence results; 34 relative BA studies showing comparable PK parameters, and 39 relative BA studies showing differences in PK parameters between test and reference products. Based on the above studies, common putative risk factors associated with differences in relative bioavailability (DRBA) in pediatric populations include age-related absorption effects, high inter-individual variability, and poor study design. A database containing 79 clinical studies on BE or relative BA in pediatrics has been developed. Putative risk factors associated with DRBA in pediatric populations are summarized.

Oxygen uptake, heart rate and activities of locomotor muscles during a critical swimming speed protocol in the gilthead sea bream Sparus aurata - Mouniboudine Hachim; Tristan Rouyer; Gilbert Dutto; Vincent Kerzerho; Serge Bernard; Jérôme Bourjea; David J. McKenzie (Journal of Fish Biology, 2021)
Oxygen uptake, heart rate and contraction frequencies of slow oxidative (SO) and fast glycolytic (FG) muscle were measured simultaneously in gilthead seabream Sparus aurata submitted to stepwise increases in current speed in a swimming respirometer. Variation in oxygen uptake was closely related to variation in heart rate, over initial steps these rose in concert with an increase in contraction frequency of SO muscle. There was an asymptote in oxygen uptake and heart rate at high speeds that reflected a transition from exclusive use of aerobic SO muscle to a combination of SO and anaerobic FG muscle, and which preceded fatigue.

Indium distribution in sphalerite from sulfide–oxide–silicate skarn assemblages: a case study of the Dulong Zn–Sn–In deposit, Southwest China - Jing Xu; Nigel J. Cook; Cristiana L. Ciobanu; Xiaofeng Li; Alkiviadis Kontonikas-Charos; Sarah Gilbert; Youhu Lv (Mineralium Deposita, 2021)

Abundance estimation of unmarked animals based on camera‐trap data - Neil A. Gilbert; John D. J. Clare; Jennifer L. Stenglein; Benjamin Zuckerberg (Conservation Biology, 2021)
The rapid improvement of camera traps in recent decades has revolutionized biodiversity monitoring. Despite clear applications in conservation science, camera traps have seldom been used to model the abundance of unmarked animal populations. We sought to summarize the challenges facing abundance estimation of unmarked animals, compile an overview of existing analytical frameworks, and provide guidance for practitioners seeking a suitable method. When a camera records multiple detections of an unmarked animal, one cannot determine whether the images represent multiple mobile individuals or a single individual repeatedly entering the camera viewshed. Furthermore, animal movement obfuscates a clear definition of the sampling area and, as a result, the area to which an abundance estimate corresponds. Recognizing these challenges, we identified 6 analytical approaches and reviewed 927 camera‐trap studies published from 2014 to 2019 to assess the use and prevalence of each method. Only about 5% of the studies used any of the abundance‐estimation methods we identified. Most of these studies estimated local abundance or covariate relationships rather than predicting abundance or density over broader areas. Next, for each analytical approach, we compiled the data requirements, assumptions, advantages, and disadvantages to help practitioners navigate the landscape of abundance estimation methods. When seeking an appropriate method, practitioners should evaluate the life history of the focal taxa, carefully define the area of the sampling frame, and consider what types of data collection are possible. The challenge of estimating abundance of unmarked animal populations persists; although multiple methods exist, no one method is optimal for camera‐trap data under all circumstances. As analytical frameworks continue to evolve and abundance estimation of unmarked animals becomes increasingly common, camera traps will become even more important for informing conservation decision‐making.

Arsenic Exposure in Relation to Apple Consumption Among Infants in the New Hampshire Birth Cohort Study - A. J. Signes-Pastor; T. Punshon; K. L. Cottingham; B. P. Jackson; V. Sayarath; D. Gilbert-Diamond; S. Korrick; M. R. Karagas (Exposure and Health, 2020)

A Review of Overlapping Landscapes: Pseudoreplication or a Red Herring in Landscape Ecology? - Benjamin Zuckerberg; Jeremy M. Cohen; Laura A. Nunes; Jacy Bernath-Plaisted; John D. J. Clare; Neil A. Gilbert; Sofia S. Kozidis; Scott B. Maresh Nelson; Amy A. Shipley; Kimberly L. Thompson; André Desrochers (Current Landscape Ecology Reports, 2020)

Historical isolation facilitates species radiation by sexual selection: Insights from Chorthippus grasshoppers - Zachary J. Nolen; Burcin Yildirim; Iker Irisarri; Shanlin Liu; Clara Groot Crego; Daniel Buchvaldt Amby; Frieder Mayer; M. Thomas P. Gilbert; Ricardo J. Pereira (Molecular Ecology, 2020)
Theoretical and empirical studies have shown that species radiations are facilitated when a trait under divergent natural selection is also involved in sexual selection. It is yet unclear how quick and effective radiations are where assortative mating is unrelated to the ecological environment and primarily results from sexual selection. We address this question using sympatric grasshopper species of the genus Chorthippus , which have evolved strong behavioural isolation while lacking noticeable ecomorphological divergence. Mitochondrial genomes suggest that the radiation is relatively recent, dating to the mid‐Pleistocene, which leads to extensive incomplete lineage sorting throughout the mitochondrial and nuclear genomes. Nuclear data shows that hybrids are absent in sympatric localities but that all species have experienced gene flow, confirming that reproductive isolation is strong but remains incomplete. Demographic modelling is most consistent with a long period of geographic isolation, followed by secondary contact and extensive introgression. Such initial periods of geographic isolation might facilitate the association between male signaling and female preference, permitting the coexistence of sympatric species that are genetically, morphologically, and ecologically similar, but otherwise behave mostly as good biological species.

Genetic analyses of native Fusarium head blight resistance in two spring wheat populations identifies QTL near the B1, Ppd-D1, Rht-1, Vrn-1, Fhb1, Fhb2, and Fhb5 loci - Dinushika Thambugala; Anita L. Brûlé-Babel; Barbara A. Blackwell; George Fedak; Adam J. Foster; Dan MacEachern; Jeannie Gilbert; Maria Antonia Henriquez; Richard A. Martin; Brent D. McCallum; Dean Spaner; Muhammad Iqbal; et al. (Theoretical and Applied Genetics, 2020)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Effect of low temperatures on the reproduction of summer and perennial rotifers from temperate regions: ecological and life cycle implications - John J. Gilbert (Aquatic Ecology, 2020)

Climate warming moderates the impacts of introduced sportfish on multiple dimensions of prey biodiversity - Charlie J. G. Loewen; Angela L. Strecker; Benjamin Gilbert; Donald A. Jackson (Global Change Biology, 2020)
Human‐assisted introductions of exotic species are a leading cause of anthropogenic change in biodiversity; however, context dependencies and interactions with co‐occurring stressors impede our ability to predict their ecological impacts. The legacy of historical sportfish stocking in mountainous regions of western North America creates a unique, natural quasiexperiment to investigate factors moderating invasion impacts on native communities across broad geographic and environmental gradients. Here we synthesize fish stocking records and zooplankton relative abundance for 685 mountain lakes and ponds in the Cascade and Canadian Rocky Mountain Ranges, to reveal the effects of predatory sportfish introduction on multiple taxonomic, functional and phylogenetic dimensions of prey biodiversity. We demonstrate an innovative analytical approach, combining exploratory random forest machine learning with confirmatory multigroup analysis using multivariate partial least‐squares structural equation models, to generate and test hypotheses concerning environmental moderation of stocking impacts. We discovered distinct effects of stocking across different dimensions of diversity, including negligible (nonsignificant) impacts on local taxonomic richness (i.e. alpha diversity) and trophic structure, in contrast to significant declines in compositional uniqueness (i.e. beta diversity) and body size. Furthermore, we found that stocking impacts were moderated by cross‐scale interactions with climate and climate‐related land‐cover variables (e.g. factors linked to treeline position and glaciers). Interactions with physical morphometric and lithological factors were generally of lesser importance, though catchment slope and habitat size constraints were relevant in certain dimensions. Finally, applying space‐for‐time substitution, a strong antagonistic (i.e. dampening) interaction between sportfish predation and warmer temperatures suggests redundancy of their size‐selective effects, meaning that warming will lessen the consequences of introductions in the future and stocked lakes may be less impacted by subsequent warming. While both stressors drive biotic homogenization, our results have important implications for fisheries managers weighing the costs/benefits of stocking—or removing established non‐native populations—under a rapidly changing climate.

Genetic, clinical, molecular, and pathogenic aspects of the South Asian–specific polymorphic MYBPC3Δ25bp variant - Mohammed Arif; Pooneh Nabavizadeh; Taejeong Song; Darshini Desai; Rohit Singh; Sholeh Bazrafshan; Mohit Kumar; Yigang Wang; Richard J. Gilbert; Perundurai S. Dhandapany; Richard C. Becker; Evangelia G. Kranias; et al. (Biophysical Reviews, 2020)

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents - David J. McIver; Soubanh Silithammavong; Watthana Theppangna; Amethyst Gillis; Bounlom Douangngeun; Kongsy Khammavong; Sinpakone Singhalath; Veasna Duong; Philippe Buchy; Sarah H. Olson; Lucy Keatts; Amanda E. Fine; et al. (Archives of Virology, 2020)

Measuring maximum oxygen uptake with an incremental swimming test and by chasing rainbow trout to exhaustion inside a respirometry chamber yields the same results - Yangfan Zhang; Matthew J. H. Gilbert; Anthony P. Farrell (Journal of Fish Biology, 2020)
This study hypothesized that oxygen uptake ( Ṁ O 2 ) measured with a novel protocol of chasing rainbow trout Oncorhynchus mykiss to exhaustion inside a static respirometer while simultaneously monitoring Ṁ O 2 ( Ṁ O 2chase ) would generate the same and repeatable peak value as when peak active Ṁ O 2 ( Ṁ O 2active ) is measured in a critical swimming speed protocol. To reliably determine peak Ṁ O 2chase , and compare to the peak during recovery of Ṁ O 2 after a conventional chase protocol outside the respirometer ( Ṁ O 2rec ), this study applied an iterative algorithm and a minimum sampling window duration ( i.e. , 1 min based on an analysis of the variance in background and exercise Ṁ O 2 ) to account for Ṁ O 2 dynamics. In support of this hypothesis, peak Ṁ O 2active (707 ± 33 mg O 2 h −1 kg −1 ) and peak Ṁ O 2chase (663 ± 43 mg O 2 h −1 kg −1 ) were similar ( P = 0.49) and repeatable (Pearson's and Spearman's correlation test; r ≥ 0.77; P Ṁ O 2max can be independent of whether a fish is exhaustively chased inside a respirometer or swum to fatigue in a swim tunnel, provided Ṁ O 2 is analysed with an iterative algorithm and a minimum but reliable sampling window. The importance of using this analytical approach was illustrated by peak Ṁ O 2chase being 23% higher ( P P Ṁ O 2chase was 18% higher ( P Ṁ O 2rec , chasing a fish inside a static respirometer may be a better protocol for obtaining maximum Ṁ O 2 .

Modelling Eurasian beaver foraging habitat and dam suitability, for predicting the location and number of dams throughout catchments in Great Britain - Hugh A. Graham; Alan Puttock; William W. Macfarlane; Joseph M. Wheaton; Jordan T. Gilbert; Róisín Campbell-Palmer; Mark Elliott; Martin J. Gaywood; Karen Anderson; Richard E. Brazier (European Journal of Wildlife Research, 2020)
Eurasian beaver ( Castor fiber ) populations are expanding across Europe. Depending on location, beaver dams bring multiple benefits and/or require management. Using nationally available data, we developed: a Beaver Forage Index (BFI), identifying beaver foraging habitat, and a Beaver Dam Capacity (BDC) model, classifying suitability of river reaches for dam construction, to estimate location and number of dams at catchment scales. Models were executed across three catchments, in Great Britain (GB), containing beaver. An area of 6747 km 2 was analysed for BFI and 16,739 km of stream for BDC. Field surveys identified 258 km of channel containing beaver activity and 89 dams, providing data to test predictions. Models were evaluated using a categorical binomial Bayesian framework to calculate probability of foraging and dam construction. BFI and BDC models successfully categorised the use of reaches for foraging and damming, with higher scoring reaches being preferred. Highest scoring categories were ca. 31 and 79 times more likely to be used than the lowest for foraging and damming respectively. Zero-inflated negative binomial regression showed that modelled dam capacity was significantly related ( p = 0.01) to observed damming and was used to predict numbers of dams that may occur. Estimated densities of dams, averaged across each catchment, ranged from 0.4 to 1.6 dams/km, though local densities may be up to 30 dams/km. These models provide fundamental information describing the distribution of beaver foraging habitat, where dams may be constructed and how many may occur. This supports the development of policy and management concerning the reintroduction and recolonisation of beaver.

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Model-Based Characterization of the Pharmacokinetics, Target Engagement Biomarkers, and Immunomodulatory Activity of PF-06342674, a Humanized mAb Against IL-7 Receptor-α, in Adults with Type 1 Diabetes - Jason H. Williams; Chandrasekhar Udata; Bishu J. Ganguly; Samantha L. Bucktrout; Tenshang Joh; Megan Shannon; Gilbert Y. Wong; Matteo Levisetti; Pamela D. Garzone; Xu Meng (The AAPS Journal, 2020)
IL-7 receptor-α (IL-7Rα) blockade has been shown to reverse autoimmune diabetes in the non-obese diabetic mouse by promoting inhibition of effector T cells and consequently altering the balance of regulatory T (T reg ) and effector memory (T EM ) cells. PF-06342674 is a humanized monoclonal antibody that binds to and inhibits the function of IL-7Rα. In the current phase 1b study, subjects with type 1 diabetes (T1D) received subcutaneous doses of either placebo or PF-06342674 (1, 3, 8 mg/kg/q2w or 6 mg/kg/q1w) for 10 weeks and were followed up to 18 weeks. Nonlinear mixed effects models were developed to characterize the pharmacokinetics (PK), target engagement biomarkers, and immunomodulatory activity. PF-06342674 was estimated to have 20-fold more potent inhibitory effect on T EM cells relative to T reg cells resulting in a non-monotonic dose-response relationship for the T reg :T EM ratio, reaching maximum at ~ 3 mg/kg/q2w dose. Target-mediated elimination led to nonlinear PK with accelerated clearance at lower doses due to high affinity binding and rapid clearance of the drug-target complex. Doses ≥ 3 mg/kg q2w result in sustained PF-06342674 concentrations higher than the concentration of cellular IL-7 receptor and, in turn, maintain near maximal receptor occupancy over the dosing interval. The results provide important insight into the mechanism of IL-7Rα blockade and immunomodulatory activity of PF-06342674 and establish a rational framework for dose selection for subsequent clinical trials of PF-06342674. Furthermore, this analysis serves as an example of mechanistic modeling to support dose selection of a drug candidate in the early phases of development.

Species niches, not traits, determine abundance and occupancy patterns: A multi‐site synthesis - Nicholas A. C. Marino; Régis Céréghino; Benjamin Gilbert; Jana S. Petermann; Diane S. Srivastava; Paula M. de Omena; Fabiola Ospina Bautista; Laura Melissa Guzman; Gustavo Q. Romero; M. Kurtis Trzcinski; Ignacio M. Barberis; Bruno Corbara; et al. (Global Ecology and Biogeography, 2020)
Aim Locally abundant species are usually widespread, and this pattern has been related to properties of the niches and traits of species. However, such explanations fail to account for the potential of traits to determine species niches and often overlook statistical artefacts. Here, we examine how trait distinctiveness determines the abilities of species to exploit either common habitats (niche position) or a range of habitats (niche breadth) and how niche position and breadth, in turn, affect abundance and occupancy. We also examine how statistical artefacts moderate these relationships. Location Sixteen sites in the Neotropics. Time period 1993–2014. Major taxa studied Aquatic invertebrates from tank bromeliads. Methods We measured the environmental niche position and breadth of each species and calculated its trait distinctiveness as the average trait difference from all other species at each site. Then, we used a combination of structural equation models and a meta‐analytical approach to test trait–niche relationships and a null model to control for statistical artefacts. Results The trait distinctiveness of each species was unrelated to its niche properties, abundance and occupancy. In contrast, niche position was the main predictor of abundance and occupancy; species that used the most common environmental conditions found across bromeliads were locally abundant and widespread. Contributions of niche breadth to such patterns were attributable to statistical artefacts, indicating that effects of niche breadth might have been overestimated in previous studies. Main conclusions Our study reveals the generality of niche position in explaining one of the most common ecological patterns. The robustness of this result is underscored by the geographical extent of our study and our control of statistical artefacts. We call for a similar examination across other systems, which is an essential task to understand the drivers of commonness across the tree of life.

Correction to: Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

Detecting spiny dogfish in grey seal diets - Kathryn A. Ono; Cathleen M. Steinbeiser; Austin B. Coco; Matthew J. Sheehan; Abigail J. Beck; Michelle N. Dufault; Katelyn M. Gilbert; Jessica J. Antonez; Zachary H. Olson (Conservation Genetics Resources, 2019)

Effects of the Bioturbating Marine Yabby Trypaea australiensis on Sediment Properties in Sandy Sediments Receiving Mangrove Leaf Litter - Ryan J. K. Dunn; David T. Welsh; Peter R. Teasdale; Franck Gilbert; Jean-Christophe Poggiale; Nathan J. Waltham (Journal of Marine Science and Engineering, 2019)
Laboratory mesocosm incubations were undertaken to investigate the influence of burrowing shrimp Trypaea australiensis (marine yabby) on sediment reworking, physical and chemical sediment characteristics and nutrients in sandy sediments receiving mangrove (Avicennia marina) leaf litter. Mesocosms of sieved, natural T. australiensis inhabited sands, were continually flushed with fresh seawater and pre-incubated for 17 days prior to triplicates being assigned to one of four treatments; sandy sediment (S), sediment + yabbies (S+Y), sediment + leaf litter (organic matter; S+OM) and sediment + yabbies + leaf litter (S+Y+OM) and maintained for 55 days. Mangrove leaf litter was added daily to treatments S+OM and S+Y+OM. Luminophores were added to mesocosms to quantify sediment reworking. Sediment samples were collected after the pre-incubation period from a set of triplicate mesocosms to establish initial conditions prior to the imposition of the treatments and from the treatment mesocosms at the conclusion of the 55-day incubation period. Yabbies demonstrated a clear effect on sediment topography and leaf litter burial through burrow creation and maintenance, creating mounds on the sediment surface ranging in diameter from 3.4 to 12 cm. Within S+Y+OM sediments leaf litter was consistently removed from the surface to sub-surface layers with only 7.5% ± 3.6% of the total mass of leaf detritus added to the mesocosms remaining at the surface at the end of the 55-day incubation period. Yabbies significantly decreased sediment wet-bulk density and increased porosity. Additionally, T. australiensis significantly reduced sediment bio-available ammonium (NH4+bio) concentrations and altered the shape of the concentration depth profile in comparison to the non-bioturbated mesocosms, indicating influences on nutrient cycling and sediment-water fluxes. No significant changes for mean apparent biodiffusion coefficients (Db) and mean biotransport coefficients (r), were found between the bioturbated S+Y and S+Y+OM mesocosms. The findings of this study provide further evidence that T. australiensis is a key-species in shallow intertidal systems playing an important role as an ‘ecosystem engineer’ in soft-bottom habitats by significantly altering physical and chemical structures and biogeochemical function.

Attachment behavior in the rotifer Brachionus rubens: induction by Asplanchna and effect on sexual reproduction - John J. Gilbert (Hydrobiologia, 2019)

Bold New World: urbanization promotes an innate behavioral trait in a lizard - James Baxter-Gilbert; Julia L. Riley; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2019)

Food in the Sea: Size Also Matters for Pelagic Fish - Quentin Queiros; Jean-Marc Fromentin; Eric Gasset; Gilbert Dutto; Camille Huiban; Luisa Metral; Lina Leclerc; Quentin Schull; David J. McKenzie; Claire Saraux (Frontiers in Marine Science, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

The urgent need for microbiology literacy in society - Kenneth Timmis; Ricardo Cavicchioli; José Luis Garcia; Balbina Nogales; Max Chavarría; Lisa Stein; Terry J. McGenity; Nicole Webster; Brajesh K. Singh; Jo Handelsman; Victor de Lorenzo; Carla Pruzzo; et al. (Environmental Microbiology, 2019)

DNA metabarcoding—Need for robust experimental designs to draw sound ecological conclusions - Lucie Zinger; Aurélie Bonin; Inger G. Alsos; Miklós Bálint; Holly Bik; Frédéric Boyer; Anthony A. Chariton; Simon Creer; Eric Coissac; Bruce E. Deagle; Marta De Barba; Ian A. Dickie; et al. (Molecular Ecology, 2019)

Divergent developmental patterns of induced morphological defenses in rotifers and Daphnia : Ecological and evolutionary context - Howard P. Riessen; John J. Gilbert (Limnology and Oceanography, 2019)
Induced morphological defenses commonly develop in some loricate rotifers as greatly increased spine development and in many species of the cladoceran genus Daphnia as an alteration in the shape and size of its head, producing helmets, crests, and neck spines. This restructuring of the shape of these animals during development, which reduces their vulnerability to a variety of planktonic predators, involves a series of developmental challenges and potential evolutionary constraints for each specific type of defense. In this review, we examine these challenges and the divergent developmental patterns that evolved in rotifers and Daphnia in response to the particular forms of predation pressure they face in their lake and pond environments. These patterns involve differences in the sensitivity of various developmental stages to predator kairomones, the timing of when the defense is present during postembryonic development, the ability to reverse the induced defense if the predator disappears from the community, and the effect of water temperature on the induction process. The type of developmental pattern associated with each induced defense appears to have been shaped by natural selection to effectively protect the animal, at minimal cost, from the specific kind of predation pressure to which it is commonly subjected.

Predation drives recurrent convergence of an interspecies mutualism - William E. Feeney; Rohan M. Brooker; Lane N. Johnston; James D. J. Gilbert; Marc Besson; David Lecchini; Danielle L. Dixson; Peter F. Cowman; Andrea Manica (Ecology Letters, 2019)
Mutualisms are important ecological interactions that underpin much of the world's biodiversity. Predation risk has been shown to regulate mutualism dynamics in species‐specific case studies; however, we lack studies which investigate whether predation can also explain broader patterns of mutualism evolution. We report that fish‐anemone mutualisms have evolved on at least 55 occasions across 16 fish families over the past 60 million years and that adult body size is associated with the ontogenetic stage of anemone mutualisms: larger‐bodied species partner with anemones as juveniles, while smaller‐bodied species partner with anemones throughout their lives. Field and laboratory studies show that predators target smaller prey, that smaller fishes associate more with anemones, and that these relationships confer protection to small fishes. Our results indicate that predation is likely driving the recurrent convergent evolution of fish‐anemone mutualisms and suggest that similar ecological processes may have selected convergence in interspecies interactions in other animal clades.

Obituary: Siv Aina Jensen Leendertz (Born Siv Aina Jensen: 1973–2018) - Chantal Akoua-Koffi; Sandra Beermann; Sébastien Calvignac-Spencer; Emmanuel Couacy-Hymann; Helene De Nys; Bernhard Ehlers; Thomas Gillespie; Jeffrey Gilbert; Jan F. Gogarten; Sandra J. Laney; Felix Lankester; Fabian H. Leendertz; et al. (International Journal of Primatology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Freedom from Tritrichomonas foetus infection in cattle in St. Kitts - Kimberly E. Coker; Joseph J. Lim; Rebecca L. Schleisman; Christopher Vosloo; Hilari M. French; Juan C. Samper; John J. Callanan; Robert O. Gilbert; Fortune Sithole; Chaoqun Yao; Aspinas Chapwanya (Tropical Animal Health and Production, 2018)

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Runners and fighters: clutch effects and body size drive innate antipredator behaviour in hatchling lizards - James Baxter-Gilbert; Julia L. Riley; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2018)

Biophysical Approaches to Protein Folding and Disease, a satellite meeting to the IUPAB-EBSA congress - Mauro Dalla Serra; Robert J. C. Gilbert; André Matagne; Patrick England (European Biophysics Journal, 2018)

Developing new age-specific prostate-specific antigen thresholds for testing for prostate cancer - Rebecca Gilbert; Kate Tilling; Richard M. Martin; J. Athene Lane; Michael Davis; Freddie C. Hamdy; David E. Neal; Jenny L. Donovan; Chris Metcalfe (Cancer Causes & Control, 2018)

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Phosphorus dynamics and phosphatase activity of soils under corn production with supplemental irrigation in humid coastal plain region, USA - Gilbert C. Sigua; Kenneth C. Stone; Philip J. Bauer; Ariel A. Szogi (Nutrient Cycling in Agroecosystems, 2017)

Collateralization of projections from the paraventricular nucleus of the thalamus to the nucleus accumbens, bed nucleus of the stria terminalis, and central nucleus of the amygdala - Xinwen Dong; Sa Li; Gilbert J. Kirouac (Brain Structure and Function, 2017)

Implantation of subcutaneous heart rate data loggers in southern elephant seals (Mirounga leonina) - Laureline L. Chaise; William Paterson; Timothy G. Laske; Susan L. Gallon; Dominic J. McCafferty; Marc Théry; André Ancel; Caroline Gilbert (Polar Biology, 2017)

Post-diagnosis serum insulin-like growth factors in relation to dietary and lifestyle changes in the Prostate testing for cancer and Treatment (ProtecT) trial - Vanessa Er; Kalina Biernacka; Andrew J. Simpkin; Richard M. Martin; Mona Jeffreys; Pauline Emmett; Rebecca Gilbert; Kerry N. L. Avery; Eleanor Walsh; Michael Davis; Jenny L. Donovan; David E. Neal; et al. (Cancer Causes & Control, 2017)
Purpose The insulin-like growth factor (IGF) system is modifiable by diet and lifestyle, and has been linked to prostate cancer development and progression. Methods We conducted a prospective cohort study of 621 men diagnosed with localized prostate cancer to investigate the associations of dietary and lifestyle changes with post-diagnosis circulating levels of IGF-I and IGFBP-3. We used analysis of covariance to estimate the associations, controlling for baseline IGF-I or IGFBP-3, respectively. Results Mean IGF-I levels were 6.5% (95% CI −12.8, −0.3%, p = 0.04) lower in men who decreased their protein intake after diagnosis compared to men who did not change. Men who changed their fruit and vegetable intake had lower IGF-I levels compared to non-changers [Decreased intake: −10.1%, 95% CI −18.4, −1.8%, p = 0.02; Increased intake: −12.0%, 95% CI −18.4, −1.8%, p = 0.002]. IGFBP-3 was 14.6% (95% CI −24.5, −4.8%, p = 0.004) lower in men who achieved a healthy body mass index after diagnosis. Men who became inactive had 9.5% higher average IGF-I levels (95% CI 0.1, 18.9%, p = 0.05). Conclusions Decreased protein intake and body mass index, and increased physical activity and fruit and vegetable intake, following a prostate cancer diagnosis were associated with reduced post-diagnosis serum IGF-I and IGFBP-3. Counterintuitively, reduced fruit and vegetable intake was also associated with reduced IGF-I, but with weak statistical support, possibly implicating chance. If confirmed in other studies, our findings may inform potential lifestyle interventions in prostate cancer. ProtecT was registered at International Standard Randomised Controlled Trial Registry, http://isrctn.org as ISRCTN20141297.

Comment on ‘Measurement and relevance of maximum metabolic rate in fishes by Norin & Clark (2016)’ - Y. Zhang; M. J. H. Gilbert (Journal of Fish Biology, 2017)

Resting-egg hatching and early population development in rotifers: a review and a hypothesis for differences between shallow and deep waters - John J. Gilbert (Hydrobiologia, 2017)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Continuing influences of introduced hedgehogs Erinaceus europaeus as a predator of wader (Charadrii) eggs four decades after their release on the Outer Hebrides, Scotland - John Calladine; Elizabeth M. Humphreys; Lucy Gilbert; Robert W. Furness; Robert A. Robinson; Robert J. Fuller; Nick A. Littlewood; Robin J. Pakeman; Johanne Ferguson; Charles Thompson (Biological Invasions, 2017)

Quantifying rapid spatial and temporal variations of CO2 fluxes from small, lowland freshwater ponds - Peter J. Gilbert; David A. Cooke; Michael Deary; Scott Taylor; Michael J. Jeffries (Hydrobiologia, 2017)

Leeches as a source of mammalian viral DNA and RNA—a study in medicinal leeches - Marie-Louise Kampmann; Ida Bærholm Schnell; Randi Holm Jensen; Jan Axtner; Adam F. Sander; Anders J. Hansen; Mads F. Bertelsen; Alex D. Greenwood; M. Thomas P. Gilbert; Andreas Wilting (European Journal of Wildlife Research, 2017)

All in the family? Analyzing the impact of family history in addition to genotype on medullary thyroid carcinoma aggressiveness in MEN2A patients - Kristin L. Long; Carol Etzel; Thereasa Rich; Samuel Hyde; Nancy D. Perrier; Paul H. Graham; Jeffrey E. Lee; Mimi I. Hu; Gilbert J. Cote; Robert Gagel; Elizabeth G. Grubbs (Familial Cancer, 2017)

Using Optical Sensors on Gliders to Estimate Phytoplankton Carbon Concentrations and Chlorophyll-to-Carbon Ratios in the Southern Ocean - Sandy J. Thomalla; A. Gilbert Ogunkoya; Marcello Vichi; Sebastiaan Swart (Frontiers in Marine Science, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Target mediated drug disposition with drug–drug interaction, Part II: competitive and uncompetitive cases - Gilbert Koch; William J. Jusko; Johannes Schropp (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Target-mediated drug disposition with drug–drug interaction, Part I: single drug case in alternative formulations - Gilbert Koch; William J. Jusko; Johannes Schropp (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Emerging Opportunities for Landscape Ecological Modelling - Nicholas W. Synes; Calum Brown; Kevin Watts; Steven M. White; Mark A. Gilbert; Justin M. J. Travis (Current Landscape Ecology Reports, 2016)

Assessment of sulfide production risk in soil during the infiltration of domestic wastewater treated by a sulfur-utilizing denitrification process - L. Ghorbel; L. Coudert; Y. Gilbert; G. Mercier; J. F. Blais (Environmental Science and Pollution Research, 2016)

The role of substrate holding in achieving critical swimming speeds: a case study using the invasive round goby (Neogobius melanostomus) - Matthew J. H. Gilbert; Janelle M. Barbarich; Matthew Casselman; Ashley V. Kasurak; Dennis M. Higgs; Keith B. Tierney (Environmental Biology of Fishes, 2016)

Assessment of non-linear combination effect terms for drug–drug interactions - Gilbert Koch; Johannes Schropp; William J. Jusko (Journal of Pharmacokinetics and Pharmacodynamics, 2016)

The potential and pitfalls of de‐extinction - Douglas J. Richmond; Mikkel‐Holger S. Sinding; M. Thomas P. Gilbert (Zoologica Scripta, 2016)
‘De‐extinction’ is the nascent discipline that aims to one day literally revive now‐extinct species from the dead. Although we have yet to see any successful attempts to truly resurrect an extinct species, several technologies are now in place that might one day provide a plausible solution. Thus, the area is receiving increased attention from both scientists and the general public. However, how far does present technology place us from the ultimate goal? We address the state of the art of several prominent de‐extinction methods: back‐breeding, cloning, synthetic genomics and genome editing, and discuss some of the major outstanding challenges for each. We also discuss some of the wider challenges facing de‐extinction, including both what might constitute the definition of success and what might be needed to successfully take a recreated animal and confer on it the ability to establish itself back in the wild.

Hydrodynamic Radii of Ranibizumab, Aflibercept and Bevacizumab Measured by Time-Resolved Phosphorescence Anisotropy - Liisa M. Hirvonen; Gilbert O. Fruhwirth; Nishanthan Srikantha; Matthew J. Barber; James E. Neffendorf; Klaus Suhling; Timothy L. Jackson (Pharmaceutical Research, 2016)

A poor international standard for trap selectivity threatens carnivore conservation - Emilio Virgós; Jorge Lozano; Sara Cabezas-Díaz; David W. Macdonald; Andrzej Zalewski; Juan Carlos Atienza; Gilbert Proulx; William J. Ripple; Luis M. Rosalino; Margarida Santos-Reis; Paul J. Johnson; Aurelio F. Malo; et al. (Biodiversity and Conservation, 2016)

Measuring kinetic drivers of pneumolysin pore structure - Robert J. C. Gilbert; Andreas F.-P. Sonnen (European Biophysics Journal, 2016)

Overview and modeling of mechanical and thermomechanical impact of underground coal gasification exploitation - F. Laouafa; R. Farret; S. Vidal-Gilbert; J-B. Kazmierczak (Mitigation and Adaptation Strategies for Global Change, 2016)

Trends in a northern Wisconsin muskellunge fishery: results from a countywide angling contest, 1964–2010 - S. J. Gilbert; G. G. Sass (Fisheries Management and Ecology, 2016)

The communication, development, and promotion of biophysical science in a European and international context - Robert J. C. Gilbert (European Biophysics Journal, 2016)

Metastatic sympathetic paraganglioma in a patient with loss of the SDHC gene - Thereasa Rich; Michelle Jackson; Alejandro Roman-Gonzalez; Komal Shah; Gilbert J. Cote; Camilo Jimenez (Familial Cancer, 2015)

Sex-biased parental care and sexual size dimorphism in a provisioning arthropod - Jeremy Field; Gavin Shreeves; Martyn Kennedy; Selina Brace; James D. J. Gilbert (Behavioral Ecology and Sociobiology, 2015)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Road mortality potentially responsible for billions of pollinating insect deaths annually - James H. Baxter-Gilbert; Julia L. Riley; Christopher J. H. Neufeld; Jacqueline D. Litzgus; David Lesbarrères (Journal of Insect Conservation, 2015)

Elevated rates of mild cognitive impairment in HIV disease - David P. Sheppard; Jennifer E. Iudicello; Mark W. Bondi; Katie L. Doyle; Erin E. Morgan; Paul J. Massman; Paul E. Gilbert; Steven Paul Woods (Journal of NeuroVirology, 2015)

Widespread Chemical Detoxification of Alkaloid Venom by Formicine Ants - Edward G. LeBrun; Peter J. Diebold; Matthew R. Orr; Lawrence E. Gilbert (Journal of Chemical Ecology, 2015)

Arsenic hazard in Cambodian rice from a market-based survey with a case study of Preak Russey village, Kandal Province - Peter J. Gilbert; David A. Polya; David A. Cooke (Environmental Geochemistry and Health, 2015)

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

Historical anthropogenic disturbances influence patterns of non-native earthworm and plant invasions in a temperate primary forest - Robin Beauséjour; I. Tanya Handa; Martin J. Lechowicz; Benjamin Gilbert; Mark Vellend (Biological Invasions, 2015)

A whole-lake experiment to control invasive rainbow smelt (Actinoperygii, Osmeridae) via overharvest and a food web manipulation - Jereme W. Gaeta; Thomas R. Hrabik; Greg G. Sass; Brian M. Roth; Stephen J. Gilbert; M. Jake Vander Zanden (Hydrobiologia, 2015)

Visions for the North Sea: The Societal Dilemma Behind Specifying Good Environmental Status - Alison J. Gilbert; Abigail McQuatters-Gollop; Olivia Langmead; Laurence Mee; Jan Vermaat (Ambio, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

Associations of vitamin D pathway genes with circulating 25-hydroxyvitamin-D, 1,25-dihydroxyvitamin-D, and prostate cancer: a nested case–control study - Rebecca Gilbert; Carolina Bonilla; Chris Metcalfe; Sarah Lewis; David M. Evans; William D. Fraser; John P. Kemp; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. Athene Lane; George Davey Smith; et al. (Cancer Causes & Control, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Transcriptomic profiling facilitates classification of response to influenza challenge - Emma E. Davenport; Richard D. Antrobus; Patrick J. Lillie; Sarah Gilbert; Julian C. Knight (Journal of Molecular Medicine, 2015)

Orexins (hypocretins) contribute to fear and avoidance in rats exposed to a single episode of footshocks - Xiaoyu Chen; Huiying Wang; Zhang Lin; Sa Li; Yonghui Li; Hugo T. Bergen; Maria E. Vrontakis; Gilbert J. Kirouac (Brain Structure and Function, 2014)

The complete genome sequence for putative H 2 ‐ and S ‐oxidizer C andidatus Sulfuricurvum sp., assembled de novo from an aquifer‐derived metagenome - Kim M. Handley; Daniela Bartels; Edward J. O'Loughlin; Kenneth H. Williams; William L. Trimble; Kelly Skinner; Jack A. Gilbert; Narayan Desai; Elizabeth M. Glass; Tobias Paczian; Andreas Wilke; Dionysios Antonopoulos; et al. (Environmental Microbiology, 2014)
Summary We reconstructed the complete 2.4 Mb‐long genome of a previously uncultivated epsilonproteobacterium, C andidatus Sulfuricurvum sp. RIFRC ‐1, via assembly of short‐read shotgun metagenomic data using a complexity reduction approach. Genome‐based comparisons indicate the bacterium is a novel species within the S ulfuricurvum genus, which contains one cultivated representative, S . kujiense . Divergence between the species appears due in part to extensive genomic rearrangements, gene loss and chromosomal versus plasmid encoding of certain (respiratory) genes by RIFRC ‐1. Deoxyribonucleic acid for the genome was obtained from terrestrial aquifer sediment, in which RIFRC ‐1 comprised ∼ 47% of the bacterial community. Genomic evidence suggests RIFRC ‐1 is a chemolithoautotrophic diazotroph capable of deriving energy for growth by microaerobic or nitrate‐/nitric oxide‐dependent oxidation of S 0 , sulfide or sulfite or H 2 oxidation. Carbon may be fixed via the reductive tricarboxylic acid cycle. Consistent with these physiological attributes, the local aquifer was microoxic with small concentrations of available nitrate, small but elevated concentrations of reduced sulfur and NH 4 + / NH 3 ‐limited. Additionally, various mechanisms for heavy metal and metalloid tolerance and virulence point to a lifestyle well‐adapted for metal(loid)‐rich environments and a shared evolutionary past with pathogenic E psilonproteobacteria . Results expand upon recent findings highlighting the potential importance of sulfur and hydrogen metabolism in the terrestrial subsurface.

Biofiltration vs conventional activated sludge plants: what about priority and emerging pollutants removal? - R. Mailler; J. Gasperi; V. Rocher; S. Gilbert-Pawlik; D. Geara-Matta; R. Moilleron; G. Chebbo (Environmental Science and Pollution Research, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Maternal age and spine development in a rotifer: ecological implications and evolution - John J. Gilbert; Mark A. McPeek (Ecology, 2013)
Brachionus calyciflorus typically develops long, defensive spines only in response to a kairomone from the predatory rotifer, Asplanchna . However, in the absence of any environmental induction, females of some clones produce daughters with increasingly long spines as they age; late‐born individuals can have posterolateral spines as long as those induced by Asplanchna : up to 50% or more of body length. Here, we construct a model using data from life‐table and predator–prey experiments to assess how this maternal‐age effect can influence the distribution of spine lengths in reproducing populations and provide defense against Asplanchna predation. When Asplanchna is absent, the frequency of individuals with late birth orders rapidly becomes extremely low; thus, any cost associated with the production of long‐spined individuals is minimal. When Asplanchna is present at densities too low for spine induction, and preys selectively on individuals with no or short posterolateral spines, the frequency of long‐spined individuals rapidly increases until a stable birth‐order structure is reached. As a result, mortality from Asplanchna predation is greatly reduced. The pronounced and novel birth‐order effect in this rotifer appears to be an effective bet‐hedging strategy to limit predation by Asplanchna when its kairomone induces no or less than maximal spine development.

Underground signals carried through common mycelial networks warn neighbouring plants of aphid attack - Zdenka Babikova; Lucy Gilbert; Toby J. A. Bruce; Michael Birkett; John C. Caulfield; Christine Woodcock; John A. Pickett; David Johnson (Ecology Letters, 2013)
The roots of most land plants are colonised by mycorrhizal fungi that provide mineral nutrients in exchange for carbon. Here, we show that mycorrhizal mycelia can also act as a conduit for signalling between plants, acting as an early warning system for herbivore attack. Insect herbivory causes systemic changes in the production of plant volatiles, particularly methyl salicylate, making bean plants, Vicia faba , repellent to aphids but attractive to aphid enemies such as parasitoids. We demonstrate that these effects can also occur in aphid‐free plants but only when they are connected to aphid‐infested plants via a common mycorrhizal mycelial network. This underground messaging system allows neighbouring plants to invoke herbivore defences before attack. Our findings demonstrate that common mycorrhizal mycelial networks can determine the outcome of multitrophic interactions by communicating information on herbivore attack between plants, thereby influencing the behaviour of both herbivores and their natural enemies.

Men with prostate cancer make positive dietary changes following diagnosis and treatment - Kerry N. L. Avery; Jenny L. Donovan; Rebecca Gilbert; Michael Davis; Pauline Emmett; Liz Down; Steven Oliver; David E. Neal; Freddie C. Hamdy; J. Athene Lane (Cancer Causes & Control, 2013)

Ceratocystis species, including two new taxa, from Eucalyptus trees in South Africa - Gilbert Kamgan Nkuekam; Michael J. Wingfield; Jolanda Roux (Australasian Plant Pathology, 2013)

Corrigendum - Kimberly J. Gilbert; Rose L. Andrew; Dan G. Bock; Michelle T. Franklin; Nolan C. Kane; Jean‐Sébastien Moore; Brook T. Moyers; Sébastien Renaut; Diana J. Rennison; Thor Veen; Timothy H. Vines (Molecular Ecology, 2013)

Nicotine differentially modulates antisaccade eye-gaze away from emotional stimuli in nonsmokers stratified by pre-task baseline performance - Nathaniel J. Wachter; David G. Gilbert (Psychopharmacology, 2013)

The impact of increased food availability on survival of a long‐distance migratory bird - Adam M. Seward; Colin M. Beale; Lucy Gilbert; T. Hefin Jones; Robert J. Thomas (Ecology, 2013)
Temperature‐, rainfall‐ and habitat‐driven change in food availability is one likely mechanism by which anthropogenic factors may affect animal population dynamics and species distributions. Long‐distance migratory birds must synchronize their migrations with food availability at locations hundreds or thousands of kilometers apart, so changes in the overall abundance of food or the phenology of peaks in food availability may be critical factors influencing annual survival. In this study we used experimental food supplementation at a breeding site to examine and compare the impact of changing food supply on annual survival of adult migratory birds and their offspring. We provided supplemental food to Northern Wheatears ( Oenanthe oenanthe ) breeding on Fair Isle, UK, to infer the sensitivity of annual survival to increases in natural food availability. Food‐supplemented wheatears exhibited higher rates of annual survival than control wheatears, and the strength of this effect varied with age. Food supplementation led to 1.56 times higher annual survival of juveniles and 1.22 times higher survival of adults. Survival of juveniles was related to their own food availability as fledglings, but not to whether their parents were food‐supplemented or unfed control adults. This increased survival, combined with increased breeding productivity associated with food supplementation, implies that an increase in natural food availability, of the magnitude simulated in our experiment, would increase the population growth rate of wheatears on Fair Isle from approximately λ = 0.93 (a contracting population) to λ = 1.14 (an expanding population).

Effects of acute administration of nicotinic and muscarinic cholinergic agonists and antagonists on performance in different cost–benefit decision making tasks in rats - Ian A. Mendez; Ryan J. Gilbert; Jennifer L. Bizon; Barry Setlow (Psychopharmacology, 2012)

Predator-induced defense in rotifers: developmental lags for morph transformations, and effect on population growth - John J. Gilbert (Aquatic Ecology, 2012)

Associations of circulating retinol, vitamin E, and 1,25-dihydroxyvitamin D with prostate cancer diagnosis, stage, and grade - Rebecca Gilbert; Chris Metcalfe; William D. Fraser; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Richard M. Martin (Cancer Causes & Control, 2012)

Comment on sea lion population viability analysis - Paul A. Breen; David J. Gilbert; Paul J. Starr (Polar Biology, 2012)

Multivariate Analysis of an LA-ICP-MS Trace Element Dataset for Pyrite - Lyron Winderbaum; Cristiana L. Ciobanu; Nigel J. Cook; Matthew Paul; Andrew Metcalfe; Sarah Gilbert (Mathematical Geosciences, 2012)

Recommendations for utilizing and reporting population genetic analyses: the reproducibility of genetic clustering using the program structure - Kimberly J. Gilbert; Rose L. Andrew; Dan G. Bock; Michelle T. Franklin; Nolan C. Kane; Jean‐Sébastien Moore; Brook T. Moyers; Sébastien Renaut; Diana J. Rennison; Thor Veen; Timothy H. Vines (Molecular Ecology, 2012)
Reproducibility is the benchmark for results and conclusions drawn from scientific studies, but systematic studies on the reproducibility of scientific results are surprisingly rare. Moreover, many modern statistical methods make use of ‘random walk’ model fitting procedures, and these are inherently stochastic in their output. Does the combination of these statistical procedures and current standards of data archiving and method reporting permit the reproduction of the authors' results? To test this, we reanalysed data sets gathered from papers using the software package structure to identify genetically similar clusters of individuals. We find that reproducing structure results can be difficult despite the straightforward requirements of the program. Our results indicate that 30% of analyses were unable to reproduce the same number of population clusters. To improve this, we make recommendations for future use of the software and for reporting structure analyses and results in published works.

Bayesian inference of a complex invasion history revealed by nuclear and chloroplast genetic diversity in the colonizing plant, S ilene latifolia - Stephen R. Keller; Kimberly J. Gilbert; Peter D. Fields; Douglas R. Taylor (Molecular Ecology, 2012)
Species invading new ranges are subject to a series of demographic events that can strongly shape genetic diversity. Describing this demographic history is important for understanding where invasive species come from and how they spread, and is critical to testing hypotheses of postinvasion adaptation. Here, we analyse nuclear and chloroplast genetic diversity to study the invasion history of the widespread colonizing weed, S ilene latifolia ( C aryophyllaceae). Bayesian clustering and PCA revealed strong population structure in the native range of Europe, and although genotypes from multiple native sources were present in the introduced range of North America, the spatial distribution of genetic variance was dramatically reorganized. Using approximate B ayesian computation ( ABC ), we compared support for different invasion scenarios, including the number and size of independent introduction events and the amount of admixture occurring between sources of introduced genotypes. Our results supported independent introductions into eastern and western North America, with the latter forming a bridgehead for a secondary invasion into the G reat L akes region of central N orth A merica. Despite small estimated founder population sizes, the duration of the demographic bottleneck after the initial introduction appeared extremely short‐lived. This pattern of repeated colonization and rapid expansion has effectively eroded the strong population structure and cytonuclear associations present in Europe, but has retained overall high genetic diversity since invasion. Our results highlight the flexibility of the ABC approach for constructing a narrative of the demographic history of species invasions and provide baseline for future studies of evolutionary changes in introduced S. latifolia populations.

Mind the gap: a comparative study of migratory behavior in social amoebae - Owen M. Gilbert; Jennie J. Kuzdzal-Fick; David C. Queller; Joan E. Strassmann (Behavioral Ecology and Sociobiology, 2012)

Microbial consortia increase thermal tolerance of corals - Justine A. Gilbert; Ross Hill; Martina A. Doblin; Peter J. Ralph (Marine Biology, 2012)

The introduction of the fire ant parasitoid Pseudacteon nocens in North America: challenges when establishing small populations - Robert M. Plowes; Patricia J. Folgarait; Lawrence E. Gilbert (BioControl, 2012)

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

Model‐based comparisons of phylogeographic scenarios resolve the intraspecific divergence of cactophilic Drosophila mojavensis - GILBERT SMITH; KONRAD LOHSE; WILLIAM J. ETGES; MICHAEL G. RITCHIE (Molecular Ecology, 2012)
The cactophilic fly Drosophila mojavensis exhibits considerable intraspecific genetic structure across allopatric geographic regions and shows associations with different host cactus species across its range. The divergence between these populations has been studied for more than 60 years, yet their exact historical relationships have not been resolved. We analysed sequence data from 15 intronic X‐linked loci across populations from Baja California, mainland Sonora‐Arizona and Mojave Desert regions under an isolation‐with‐migration model to assess multiple scenarios of divergence. We also compared the results with a pre‐existing sequence data set of eight autosomal loci. We derived a population tree with Baja California placed at its base and link their isolation to Pleistocene climatic oscillations. Our estimates suggest the Baja California population diverged from an ancestral Mojave Desert/mainland Sonora‐Arizona group around 230 000–270 000 years ago, while the split between the Mojave Desert and mainland Sonora‐Arizona populations occurred one glacial cycle later, 117 000–135 000 years ago. Although we found these three populations to be effectively allopatric, model ranking could not rule out the possibility of a low level of gene flow between two of them. Finally, the Mojave Desert population showed a small effective population size, consistent with a historical population bottleneck. We show that model‐based inference from multiple loci can provide accurate information on the historical relationships of closely related groups allowing us to set into historical context a classic system of incipient ecological speciation.

A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom - Nicholas J. Young; Chris Metcalfe; David Gunnell; Mari-Anne Rowlands; J. Athene Lane; Rebecca Gilbert; Kerry N. L. Avery; Michael Davis; David E. Neal; Freddie C. Hamdy; Jenny Donovan; Richard M. Martin; et al. (Cancer Causes & Control, 2012)

Variability and directionality of temporal changes in δ13C and δ15N of aquatic invertebrate primary consumers - Ryan J. Woodland; Pierre Magnan; Hélène Glémet; Marco A. Rodríguez; Gilbert Cabana (Oecologia, 2012)

Lemming winter habitat choice: a snow-fencing experiment - Donald G. Reid; Frédéric Bilodeau; Charles J. Krebs; Gilles Gauthier; Alice J. Kenney; B. Scott Gilbert; Maria C.-Y. Leung; David Duchesne; Elizabeth Hofer (Oecologia, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Predictors of 25-hydroxyvitamin D and its association with risk factors for prostate cancer: evidence from the Prostate testing for cancer and Treatment study - Rebecca Gilbert; Richard M. Martin; William D. Fraser; Sarah Lewis; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Chris Metcalfe (Cancer Causes & Control, 2012)

Sources of inputs to the anterior and posterior aspects of the paraventricular nucleus of the thalamus - Sa Li; Gilbert J. Kirouac (Brain Structure and Function, 2012)

Mind the gap: the ratio of yolk androgens and antioxidants varies between sons and daughters dependent on paternal attractiveness - E. C. Pariser; L. Gilbert; N. Hazon; K. E. Arnold; J. A. Graves (Behavioral Ecology and Sociobiology, 2012)

SLC39A2 and FSIP1 polymorphisms as potential modifiers of arsenic-related bladder cancer - Margaret R. Karagas; Angeline S. Andrew; Heather H. Nelson; Zhongze Li; Tracy Punshon; Alan Schned; Carmen J. Marsit; J. Steven Morris; Jason H. Moore; Anna L. Tyler; Diane Gilbert-Diamond; Mary-Lou Guerinot; et al. (Human Genetics, 2012)

Natural outbreak of Streptococcus agalactiae (GBS) infection in wild giant Queensland grouper, Epinephelus lanceolatus (Bloch), and other wild fish in northern Queensland, Australia - R O Bowater; J Forbes‐Faulkner; I G Anderson; K Condon; B Robinson; F Kong; G L Gilbert; A Reynolds; S Hyland; G McPherson; J O’ Brien; D Blyde (Journal of Fish Diseases, 2012)
Ninety‐three giant Queensland grouper, Epinephelus lanceolatus (Bloch), were found dead in Queensland, Australia, from 2007 to 2011. Most dead fish occurred in northern Queensland, with a peak of mortalities in Cairns in June 2008. In 2009, sick wild fish including giant sea catfish, Arius thalassinus (Rüppell), and javelin grunter, Pomadasys kaakan (Cuvier), also occurred in Cairns. In 2009 and 2010, two disease epizootics involving wild stingrays occurred at Sea World marine aquarium. Necropsy, histopathology, bacteriology and PCR determined that the cause of deaths of 12 giant Queensland grouper, three wild fish, six estuary rays, Dasyatis fluviorum (Ogilby), one mangrove whipray, Himantura granulata (Macleay), and one eastern shovelnose ray, Aptychotrema rostrata (Shaw), was Streptococcus agalactiae septicaemia. Biochemical testing of 34 S. agalactiae isolates from giant Queensland grouper, wild fish and stingrays showed all had identical biochemical profiles. The 16S rRNA gene sequences of isolates confirmed all isolates were S. agalactiae ; genotyping of selected S. agalactiae isolates showed the isolates from giant Queensland grouper were serotype Ib, whereas isolates from wild fish and stingrays closely resembled serotype II. This is the first report of S. agalactiae from wild giant Queensland grouper and other wild tropical fish and stingray species in Queensland, Australia.

Mitochondrial Haplogroup X is associated with successful aging in the Amish - Monique D. Courtenay; John R. Gilbert; Lan Jiang; Anna C. Cummings; Paul J. Gallins; Laura Caywood; Lori Reinhart-Mercer; Denise Fuzzell; Claire Knebusch; Renee Laux; Jacob L. McCauley; Charles E. Jackson; et al. (Human Genetics, 2012)

Ceratocystis species, including two new species associated with nitidulid beetles, on eucalypts in Australia - Gilbert Kamgan Nkuekam; Michael J. Wingfield; Caroline Mohammed; Angus J. Carnegie; Geoff S. Pegg; Jolanda Roux (Antonie van Leeuwenhoek, 2012)

Variation in wind and piscivorous predator fields affecting the survival of Atlantic salmon, Salmo salar , in the Gulf of Maine - K. D. FRIEDLAND; J. P. MANNING; J. S. LINK; J. R. GILBERT; A. T. GILBERT; A. F. O’CONNELL (Fisheries Management and Ecology, 2012)
Observations relevant to the North American stock complex of Atlantic salmon, Salmo salar L., suggest that marine mortality is influenced by variation in predation pressure affecting post‐smolts during the first months at sea. This hypothesis was tested for Gulf of Maine (GOM) stocks by examining wind pseudostress and the distribution of piscivorous predator fields potentially affecting post‐smolts. Marine survival has declined over recent decades with a change in the direction of spring winds, which is likely extending the migration of post‐smolts by favouring routes using the western GOM. In addition to changes in spring wind patterns, higher spring sea surface temperatures have been associated with shifting distributions of a range of fish species. The abundance of several pelagic piscivores, which based on their feeding habits may predate on salmon post‐smolts, has increased in the areas that serve as migration corridors for post‐smolts. In particular, populations of silver hake, Merluccius bilinearis (Mitchell), red hake, Urophycis chuss (Walbaum), and spiny dogfish, Squalus acanthias L., increased in size in the portion of the GOM used by post‐smolts. Climate variation and shifting predator distributions in the GOM are consistent with the predator hypothesis of recruitment control suggested for the stock complex.

Incorporating temporally dynamic baselines in isotopic mixing models - Ryan J. Woodland; Marco A. Rodríguez; Pierre Magnan; Hélène Glémet; Gilbert Cabana (Ecology, 2012)
Stable isotopes (particularly C and N) are widely used to make inferences regarding food web structure and the phenology of consumer diet shifts, applications that require accurate isotopic characterization of trophic resources to avoid biased inferences of feeding relationships. For example, most isotope mixing models require that endmembers be adequately represented by a single probability distribution; yet, there is mounting evidence that the isotopic composition of aquatic organisms often used as mixing model endmembers can change over periods of weeks to months. A review of the literature indicated that the δ 13 C values of five aquatic primary consumer taxa, commonly used as proxies of carbon production sources (i.e., trophic baselines), express seasonally dynamic cycles characterized by an oscillation between summer maxima and winter minima. Based on these results, we built a dynamic baseline mixing model that allows a growing consumer to track temporal gradients in the isotopic baselines of a food web. Simulations showed that the ability of a consumer to maintain or approach isotopic equilibrium with its diet over a realistic growth season was strongly affected by both the rate of change of the isotopic baseline and equilibration rate of the consumer. In an empirical application, mixing models of varying complexity were used to estimate the relative contribution of benthic vs. pelagic carbon sources to nine species of juvenile fish in a fluvial lake of the St. Lawrence River system (Québec, Canada). Estimates of p (proportion of carbon derived from benthic sources) derived from a static mixing model indicated broad interspecific variation in trophic niche, ranging from complete benthivory to >95% reliance on pelagic food webs. Output from the more realistic dynamic baseline mixing model increased estimated benthivory by an average of 36% among species. Taken together, our results demonstrate that failing to identify dynamic baselines when present, and (or) matching consumers with baseline taxa that possess substantially different equilibration rates can seriously bias interpretation of stable isotope data. Additionally, by providing a formalized framework that allows both resources and consumers to shift their isotopic value through time, our model demonstrates a feasible approach for incorporating temporally dynamic isotope conditions in trophic studies of higher consumers.

Erratum to: Molecular characterization of the translocation breakpoints in the Down syndrome mouse model Ts65Dn - Laura G. Reinholdt; Yueming Ding; Griffith J. Gilbert; Anne Czechanski; Jeffrey P. Solzak; Randall J. Roper; Mark T. Johnson; Leah Rae Donahue; Cathleen Lutz; Muriel T. Davisson (Mammalian Genome, 2011)

Molecular characterization of the translocation breakpoints in the Down syndrome mouse model Ts65Dn - Laura G. Reinholdt; Yueming Ding; Griffith T. Gilbert; Anne Czechanski; Jeffrey P. Solzak; Randall J. Roper; Mark T. Johnson; Leah Rae Donahue; Cathleen Lutz; Muriel T. Davisson (Mammalian Genome, 2011)

Temperature, kairomones, and phenotypic plasticity in the rotifer Keratella tropica (Apstein, 1907) - John J. Gilbert (Hydrobiologia, 2011)

Trends and low-frequency variability of storminess over western Europe, 1878–2007 - Xiaolan L. Wang; Hui Wan; Francis W. Zwiers; Val R. Swail; Gilbert P. Compo; Robert J. Allan; Russell S. Vose; Sylvie Jourdain; Xungang Yin (Climate Dynamics, 2011)

The effect of landscape heterogeneity and host movement on a tick-borne pathogen - Edward O. Jones; Steven D. Webb; Francisco J. Ruiz-Fons; Steven Albon; Lucy Gilbert (Theoretical Ecology, 2011)

Assessing phytoremediation potentials of selected tropical plants for acrylamide - Annie Melinda Paz-Alberto; Ma. Johanna J. De Dios; Ronaldo T. Alberto; Gilbert C. Sigua (Journal of Soils and Sediments, 2011)

Spatial gradients of methylmercury for breeding common loons in the Laurentian Great Lakes region - David C. Evers; Kathryn A. Williams; Michael W. Meyer; Anton M. Scheuhammer; Nina Schoch; Andrew T. Gilbert; Lori Siegel; Robert J. Taylor; Robert Poppenga; Christopher R. Perkins (Ecotoxicology, 2011)

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Experimental climate effect on seasonal variability of polyphenol/phenoloxidase interplay along a narrow fen–bog ecological gradient in Sphagnum fallax - VINCENT E. J. JASSEY; GENEVIÈVE CHIAPUSIO; DANIEL GILBERT; ALEXANDRE BUTTLER; MARIE‐LAURE TOUSSAINT; PHILIPPE BINET (Global Change Biology, 2011)
Extracellular phenoloxidase enzymes play an important role in the stability of soil carbon storage by contributing to the cycling of complex recalcitrant phenolic compounds. Climate warming could affect peatland functioning through an alteration of polyphenol/phenoloxidase interplay, which could lead them to becoming weaker sinks of carbon. Here, we assessed the seasonal variability of total phenolics and phenoloxidases subjected to 2–3 °C increase in air temperature using open‐top chambers. The measurements were performed along a narrow fen–bog ecological gradient over one growing season. Climate warming had a weak effect on phenoloxidases, but reduced phenolics in both fen and bog areas. Multivariate analyses revealed a split between the areas and also showed that climate warming exacerbated the seasonal variability of polyphenols, culminating in a destabilization of the carbon cycle. A negative relationship between polyphenols and phenoloxidases was recorded in controls and climate treatments suggesting an inhibitory effect of phenolics on phenoloxidases. Any significant decrease of phenolics through repeatedly elevated temperature would greatly impact the ecosystem functioning and carbon cycle through an alteration of the interaction of polyphenols with microbial communities and the production of extracellular enzymes. Our climate treatments did not have the same impact along the fen–bog gradient and suggested that not all the peatland habitats would respond similarly to climate forcing.

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

The Influence of Floodplain Vegetation Succession on Hydraulic Roughness: Is Ecosystem Rehabilitation in Dutch Embanked Floodplains Compatible with Flood Safety Standards? - Bart Makaske; Gilbert J. Maas; Claus van den Brink; Henk P. Wolfert (Ambio, 2011)

The combined effect of waterlogging, extractable P and soil pH on α-diversity: a case study on mesotrophic grasslands in the UK - Dana Michalcová; Joanne C. Gilbert; Clare S. Lawson; David J. G. Gowing; Rob H. Marrs (Plant Ecology, 2011)

Preface - Norbert Walz; Rita Adrian; John J. Gilbert; Michael T. Monaghan; Guntram Weithoff; Heike Zimmermann-Timm (Hydrobiologia, 2011)

In memoriam - Norbert Walz; Károly Schöll; Robert L. Wallace; John J. Gilbert; Pierre Clément; Claude Rougier (Hydrobiologia, 2011)

Daphnia–rotifer interactions in Patagonian communities - María C. Diéguez; John J. Gilbert (Hydrobiologia, 2011)

In vitro hepatoprotective and antioxidant activities of crude extract and isolated compounds from Ficus gnaphalocarpa - Donfack J. Hubert; Amadou Dawe; Ngueguim T. Florence; Kapche D. W. F. Gilbert; Tchana N. Angele; D. Buonocore; P. Vita Finzi; G. Vidari; Ngadjui T. Bonaventure; Fulvio Marzatico; Moundipa F. Paul (Inflammopharmacology, 2011)

The relation between adiposity throughout the life course and variation in IGFs and IGFBPs: evidence from the ProtecT (Prostate testing for cancer and Treatment) study - Mari-Anne Rowlands; Jeff M. P. Holly; David Gunnell; Rebecca Gilbert; Jenny Donovan; J. Athene Lane; Gemma Marsden; Simon M. Collin; Freddie Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2010)

Factors Influencing Safety Among a Group of Commercial Fishermen Along the Texas Gulf Coast - Jeffrey L. Levin; Karen Gilmore; Sara Shepherd; Amanda Wickman; Ann Carruth; J. Torey Nalbone; Gilbert Gallardo; Matthew W. Nonnenmann (Journal of Agromedicine, 2010)

Accumulation Capacities of Particulate Matter in an Acrocarpous and a Pleurocarpous Moss Exposed at Three Differently Polluted Sites (Industrial, Urban and Rural) - J. Fabure; C. Meyer; F. Denayer; A. Gaudry; D. Gilbert; N. Bernard (Water, Air, & Soil Pollution, 2010)

Orexins in the paraventricular nucleus of the thalamus mediate anxiety-like responses in rats - Yonghui Li; Sa Li; Chuguang Wei; Huiying Wang; Nan Sui; Gilbert J. Kirouac (Psychopharmacology, 2010)

Erratum to: Resolving Myoarchitectural Disarray in the Mouse Ventricular Wall with Diffusion Spectrum Magnetic Resonance Imaging - Teresa T. Wang; Hyuk Sang Kwon; Guangping Dai; Ruopeng Wang; Srboljub M. Mijailovich; Richard L. Moss; Peter T. C. So; Van J. Wedeen; Richard J. Gilbert (Annals of Biomedical Engineering, 2010)

Resource allocation for efficient environmental management - Michael A. McCarthy; Colin J. Thompson; Cindy Hauser; Mark A. Burgman; Hugh P. Possingham; Melinda L. Moir; Thanawat Tiensin; Marius Gilbert (Ecology Letters, 2010)
Ecology Letters (2010) Abstract Environmental managers must decide how to invest available resources. Researchers have previously determined how to allocate conservation resources among regions, design nature reserves, allocate funding to species conservation programs, design biodiversity surveys and monitoring programs, manage species and invest in greenhouse gas mitigation schemes. However, these issues have not been addressed with a unified theory. Furthermore, uncertainty is prevalent in environmental management, and needs to be considered to manage risks. We present a theory for optimal environmental management, synthesizing previous approaches to the topic and incorporating uncertainty. We show that the theory solves a diverse range of important problems of resource allocation, including distributing conservation resources among the world’s biodiversity hotspots; surveillance to detect the highly pathogenic avian influenza H5N1 virus in Thailand; and choosing survey methods for the insect order Hemiptera. Environmental management decisions are similar to decisions about financial investments, with trade‐offs between risk and reward.

Resolving Myoarchitectural Disarray in the Mouse Ventricular Wall with Diffusion Spectrum Magnetic Resonance Imaging - Teresa T. Wang; Hyuk Sang Kwon; Guangping Dai; Ruopeng Wang; Srboljub M. Mijailovich; Richard L. Moss; Peter T. C. So; Van J. Wedeen; Richard J. Gilbert (Annals of Biomedical Engineering, 2010)

Response of testate amoeba assemblages to environmental and climatic changes during the Lateglacial–Holocene transition at Lake Lautrey (Jura Mountains, eastern France) - Adeline A. J. Wall; Michel Magny; Edward A. D. Mitchell; Boris Vannière; Daniel Gilbert (Journal of Quaternary Science, 2010)
We tested the response of lacustrine testate amoebae (thecamoebians) to climate and environmental changes for the Lateglacial–Holocene transition. The palaeoenvironmental history of the study site (Lake Lautrey, Jura Mountains, eastern France) was previously established based on high‐resolution multi‐proxy studies of the same core. The present study is characterised by a high taxonomic resolution (54 taxa), inclusion of small species (down to 25 µm) and high total counts (>500 individuals per sample on average). Changes in the composition of testate amoeba assemblages (dominant species and assemblage structure), as well as in the accumulation rate (tests cm −2 a −1 ), corresponded to major climatic phases (i.e. Oldest Dryas, Bølling–Allerød Interstadial, Younger Dryas, Preboreal) as well as changes in organic matter inputs. Furthermore, decreases in the accumulation rate characterised minor short‐lived cooling events, such as Older Dryas event or Gerzensee oscillation. However, the Preboreal oscillation, which was well registered by other proxies at Lake Lautrey, could not be recognised in the testate amoeba record. This work demonstrates that lacustrine testate amoebae can be used for palaeoclimatic and palaeoecological reconstructions. Nevertheless, a better understanding of the relation between climate, organic matter and lacustrine testate amoebae requires further high‐resolution studies based on multi‐proxy approaches and the development of appropriate modern analogues. Copyright © 2010 John Wiley & Sons, Ltd.

Distribution patterns of wintering sea ducks in relation to the North Atlantic Oscillation and local environmental characteristics - Elise F. Zipkin; Beth Gardner; Andrew T. Gilbert; Allan F. O’Connell; J. Andrew Royle; Emily D. Silverman (Oecologia, 2010)

Optimization of the Water-Insoluble Procedures for USP General Chapter Residual Solvents - Jennifer L. Belsky; Alyssa J. Ashley; Premal A. Bhatt; Karen V. Gilbert; Heather R. Joyce; Chunhua Pan; Horacio Pappa; Samir Z. Wahab (AAPS PharmSciTech, 2010)

Environmental Radioxenon Levels in Europe: a Comprehensive Overview - Paul R. J. Saey; Clemens Schlosser; Pascal Achim; Matthias Auer; Anders Axelsson; Andreas Becker; Xavier Blanchard; Guy Brachet; Luis Cella; Lars-Erik De Geer; Martin B. Kalinowski; Gilbert Le Petit; et al. (Pure and Applied Geophysics, 2010)

Testate amoeba analysis of lake sediments: impact of filter size and total count on estimates of density, species richness and assemblage structure - A. A. J. Wall; D. Gilbert; M. Magny; E. A. D. Mitchell (Journal of Paleolimnology, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Mechanical damage to pollen aids nutrient acquisition in Heliconius butterflies (Nymphalidae) - Harald W. Krenn; Monika J. B. Eberhard; Stefan H. Eberhard; Anna-Laetitia Hikl; Werner Huber; Lawrence E. Gilbert (Arthropod-Plant Interactions, 2009)

Gigantism of the Australian Diprotodon Owen 1838 (Marsupialia, Diprotodontoidea) through the Pleistocene - Gilbert J. Price; Katarzyna J. Piper (Journal of Quaternary Science, 2009)
Diprotodon Owen, was one of the first fossil mammals described from Australia and has the distinction of being the largest ever marsupial. However, until recently its taxonomy was unclear and knowledge of its continental distribution, palaeoecology and evolution was poorly known. This paper describes cranial elements from an unusually small‐bodied Diprotodon from the Early Pleistocene Nelson Bay Formation, Portland, Australia. It is intermediate in size between the smaller‐bodied Pliocene ancestor, Euryzygoma dunense de Vis 1895 and the larger‐bodied Late Pleistocene D. optatum Owen, . However, it is morphologically inseparable from Late Pleistocene Diprotodon and is here referred to as D. ?optatum . A temporal morphocline most parsimoniously explains the medium body size of the Nelson Bay taxon; thus we provide the first evidence of a transitional form within Diprotodon . The cause(s) of gigantism of the E. dunense – D. ?optatum – D. optatum lineage through the late Cainozoic is unclear but most likely involved the physiological response to changes in the physical and/or biotic environment. Although the size changes within the lineage may have been initially advantageous, they were most likely disadvantageous when the optimum body size was obtained. Our results suggest that Diprotodon was at its largest ever body size during the Late Pleistocene – the time period that coincided with its extinction. Copyright © 2009 John Wiley & Sons, Ltd.

The seasonal structure of microbial communities in the Western English Channel - Jack A. Gilbert; Dawn Field; Paul Swift; Lindsay Newbold; Anna Oliver; Tim Smyth; Paul J. Somerfield; Sue Huse; Ian Joint (Environmental Microbiology, 2009)
Summary Very few marine microbial communities are well characterized even with the weight of research effort presently devoted to it. Only a small proportion of this effort has been aimed at investigating temporal community structure. Here we present the first report of the application of high‐throughput pyrosequencing to investigate intra‐annual bacterial community structure. Microbial diversity was determined for 12 time points at the surface of the L4 sampling site in the Western English Channel. This was performed over 11 months during 2007. A total of 182 560 sequences from the V6 hyper‐variable region of the small‐subunit ribosomal RNA gene (16S rRNA) were obtained; there were between 11 327 and 17 339 reads per sample. Approximately 7000 genera were identified, with one in every 25 reads being attributed to a new genus; yet this level of sampling far from exhausted the total diversity present at any one time point. The total data set contained 17 673 unique sequences. Only 93 (0.5%) were found at all time points, yet these few lineages comprised 50% of the total reads sequenced. The most abundant phylum was Proteobacteria ( 50% of all sequenced reads), while the SAR11 clade comprised 21% of the ubiquitous reads and ∼12% of the total sequenced reads. In contrast, 78% of all operational taxonomic units were only found at one time point and 67% were only found once, evidence of a large and transient rare assemblage. This time series shows evidence of seasonally structured community diversity. There is also evidence for seasonal succession, primarily reflecting changes among dominant taxa. These changes in structure were significantly correlated to a combination of temperature, phosphate and silicate concentrations.

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

Aerobic respiration and hypoxia in the Lower St. Lawrence Estuary: Stable isotope ratios of dissolved oxygen constrain oxygen sink partitioning - Moritz F. Lehmann; Bruce Barnett; Y. Gélinas; Denis Gilbert; Roxane J. Maranger; Alfonso Mucci; Bjorn Sundby; Benoit Thibodeau (Limnology and Oceanography, 2009)
We measured the concentration and the stable isotope ratios of dissolved oxygen in the water column in the Estuary and Gulf of St. Lawrence to determine the relative importance of pelagic and benthic dissolved oxygen respiration to the development of hypoxic deep waters. The progressive landward decrease of dissolved oxygen in the bottom waters along the axis of the Laurentian Channel (LC) is accompanied by an increase in the 18 O: 16 O ratio, as would be expected from O‐isotope fractionation associated with bacterial oxygen respiration. The apparent O‐isotope effect, ε O‐app , of 10.8% reveals that community O‐isotope fractionation is significantly smaller than if bacterial respiration occurred solely in the water column. Our observation can best be explained by a contribution of benthic O 2 consumption occurring with a strongly reduced O‐isotope effect at the scale of sediment‐water exchange (ε O‐sed ~ 7%). The value for ε O‐sed was estimated from benthic O 2 exchange simulations using a one‐dimensional diffusion‐reaction O‐isotope model. Adopting this ε O‐sed value, and given the observed community O‐isotope fractionation, we calculate that approximately two thirds of the ecosystem respiration occurs within the sediment, in reasonable agreement with direct respiration measurements. Based on the difference between dissolved oxygen concentrations in the deep waters of the Lower St. Lawrence Estuary and in the water that enters the LC at Cabot Strait, we estimate an average respiration rate of 5500 mmol O 2 m −2 yr −1 for the 100‐m‐thick layer of bottom water along the LC, 3540 mmol O 2 m −2 yr −1 of which is attributed to bacterial benthic respiration.

Physical mapping of the elephant X chromosome: conservation of gene order over 105 million years - Claudia Leticia Rodríguez Delgado; Paul D. Waters; Clément Gilbert; Terence J. Robinson; Jennifer A. Marshall Graves (Chromosome Research, 2009)

Can Campylobacter coli induce Guillain-Barré syndrome? - A. van Belkum; B. Jacobs; E. van Beek; R. Louwen; W. van Rijs; L. Debruyne; M. Gilbert; J. Li; A. Jansz; F. Mégraud; H. Endtz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effect of photoperiod and thermoperiod on microtuberization and carbohydrate levels in Cocoyam (Xanthosoma sagittifolium L. Schott) - T. J. J. Tsafack; Gilbert P. Charles; A. Hourmant; N. D. Omokolo; M. Branchard (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Modification of planned actions - Sukhvinder S. Obhi; Shannon Matkovich; Sam J. Gilbert (Experimental Brain Research, 2009)

Modification of planned actions - Sukhvinder S. Obhi; Shannon Matkovich; Sam J. Gilbert (Experimental Brain Research, 2009)

Major dimensions in food‐web structure properties - Jan E. Vermaat; Jennifer A. Dunne; Alison J. Gilbert (Ecology, 2009)
The covariance among a range of 20 network structural properties of food webs plus net primary productivity was assessed for 14 published food webs using principal components analysis. Three primary components explained 84% of the variability in the data sets, suggesting substantial covariance among the properties employed in the literature. The first dimension explained 48% of the variance and could be ascribed to connectance, covarying significantly with the proportion of intermediate species and characteristic path length. The second dimension explained 19% and was related to trophic species richness. The third axis explained 17% and was related to ecosystem net primary productivity. A distinct opposite clustering of connectance, the proportion of intermediate species, and mean trophic level vs. the proportion of top and basal species and path length suggests a dichotomy in food‐web structure. Food webs appear either clustered and highly interconnected or elongated with fewer links.

Non-linear EEG synchronization during observation and execution of simple and complex sequential finger movements - Claire Calmels; Magaly Hars; Paul Holmes; Gilbert Jarry; Cornelis J. Stam (Experimental Brain Research, 2008)

S32006, a novel 5-HT2C receptor antagonist displaying broad-based antidepressant and anxiolytic properties in rodent models - Anne Dekeyne; Clotilde Mannoury la Cour; Alain Gobert; Mauricette Brocco; Françoise Lejeune; Florence Serres; Trevor Sharp; Annie Daszuta; Amélie Soumier; Mariusz Papp; Jean-Michel Rivet; Gunnar Flik; et al. (Psychopharmacology, 2008)

A systemic approach for the development of FHB resistant germplasm accelerates genetic progress - A. Comeau; F. Langevin; V. Caetano; S. Haber; M. Savard; H. Voldeng; G. Fedak; Y. Dion; S. Rioux; J. Gilbert; D. Somers; R. Martin (Cereal Research Communications, 2008)

Resolving the three-dimensional myoarchitecture of bovine esophageal wall with diffusion spectrum imaging and tractography - Richard J. Gilbert; Terry A. Gaige; Ruopeng Wang; Thomas Benner; Guangping Dai; Jonathan N. Glickman; Van J. Wedeen (Cell and Tissue Research, 2008)

An explosive–intrusive subglacial rhyolite eruption at Dalakvísl, Torfajökull, Iceland - H. Tuffen; D. W. McGarvie; H. Pinkerton; J. S. Gilbert; R. A. Brooker (Bulletin of Volcanology, 2008)

Pathogens promote plant diversity through a compensatory response - Devon J. Bradley; Gregory S. Gilbert; Jennifer B. H. Martiny (Ecology Letters, 2008)
Pathogens are thought to promote diversity in plant communities by preventing competitive exclusion. Previous studies have focussed primarily on single‐plant, single‐pathogen interactions, yet the interactions between multiple pathogens and multiple hosts may have non‐additive impacts on plant community composition. Here, we report that both a bacterial and a fungal pathogen maintained the diversity of a four‐species plant community across five generations; however, significant interactions between the pathogens resulted in less plant diversity when the two pathogens were present than when the fungal pathogen was present alone. Standard models predict that pathogens will maintain plant diversity when they cause a disproportionate loss of fitness in the dominant plant species. In our experiment, however, pathogens maintained plant diversity because the rare species produced more seeds through a compensatory response to pathogen infection. Finally, we found that the influence of pathogens on maintaining plant diversity was 5.5 times greater than the influence of nutrient resource heterogeneity. Pathogens may be a major factor in maintaining plant diversity, and our findings emphasize the importance of investigating the roles of pathogens in natural plant communities.

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Chromosomal evolution in tenrecs (Microgale and Oryzorictes, Tenrecidae) from the Central Highlands of Madagascar - C. Gilbert; S. M. Goodman; V. Soarimalala; L. E. Olson; P. C. M. O’Brien; F. F. B. Elder; F. Yang; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2007)

Multiple paternity in viviparous kelp rockfish, Sebastes atrovirens - Susan M. Sogard; Elizabeth Gilbert-Horvath; Eric C. Anderson; Rebecca Fisher; Steven A. Berkeley; J. Carlos Garza (Environmental Biology of Fishes, 2007)

Glaciolacustrine varved sediment as an alpine hydroclimatic proxy - K. R. Hodder; R. Gilbert; J. R. Desloges (Journal of Paleolimnology, 2007)

Promiscuous, non-catalytic, tandem carbohydrate-binding modules modulate the cell-wall structure and development of transgenic tobacco (Nicotiana tabacum) plants - Olawole O. Obembe; Evert Jacobsen; Jaap Timmers; Harry Gilbert; Anthony W. Blake; J. Paul Knox; Richard G. F. Visser; Jean-Paul Vincken (Journal of Plant Research, 2007)

Intraclonal variation in propensity for mixis in several rotifers: variation among females and with maternal age - John J. Gilbert; Thomas Schröder (Hydrobiologia, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Remnants of ancient genetic diversity preserved within captive groups of scimitar‐horned oryx ( Oryx dammah ) - A. IYENGAR; T. GILBERT; T. WOODFINE; J. M. KNOWLES; F. M. DINIZ; R. A. BRENNEMAN; E. E. LOUIS; N. MACLEAN (Molecular Ecology, 2007)
Scimitar‐horned oryx, now considered extinct in the wild, persists in large numbers in captivity. In this first molecular genetic study on this species, we explore the patterns of genetic diversity across European, North American, and a few other captive groups using microsatellite markers and mitochondrial control region sequencing. Strong population structure was not evident from microsatellite data but we discovered deep divergence within the mitochondrial DNA haplotypes from a network analysis where three disconnected networks were obtained, with estimated divergence times of c. 2.1–2.7 million years. Mismatch distribution analyses suggest population expansions c. 1.2 and 0.5 million years ago. We discuss our findings in the context of historical climatic changes in North Africa and use information obtained on current patterns of genetic diversity within captive groups to make recommendations for future captive management and reintroduction strategies.

Cortical Activity Prior to, and During, Observation and Execution of Sequential Finger Movements - Claire Calmels; Paul Holmes; Gilbert Jarry; Jean-Michel Lévèque; Magaly Hars; Cornelis J. Stam (Brain Topography, 2006)

Chromosome painting and molecular dating indicate a low rate of chromosomal evolution in golden moles (Mammalia, Chrysochloridae) - C. Gilbert; P. C. O’Brien; G. Bronner; F. Yang; A. Hassanin; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2006)

Temporal recruitment patterns and gene flow in kelp rockfish ( Sebastes atrovirens ) - ELIZABETH A. GILBERT‐HORVATH; RALPH J. LARSON; JOHN CARLOS GARZA (Molecular Ecology, 2006)
Pelagic dispersal of marine organisms provides abundant opportunity for gene flow and presumably inhibits population genetic divergence. However, ephemeral, fine‐scale, temporal and spatial genetic heterogeneity is frequently observed in settled propagules of marine species that otherwise exhibit broad‐scale genetic homogeneity. A large variance in reproductive success is one explanation for this phenomenon. Here, genetic analyses of 16 microsatellite loci are used to examine temporal patterns of variation in young‐of‐year kelp rockfish ( Sebastes atrovirens ) recruiting to nearshore habitat in Monterey Bay, California, USA. Population structure of adults from central California is also evaluated to determine if spatial structure exists and might potentially contribute to recruitment patterns. Genetic homogeneity was found among 414 young‐of‐year sampled throughout the entire 1998 recruitment season. No substantial adult population structure was found among seven populations spanning 800 km of coastline that includes the Point Conception marine biogeographic boundary. Comparison of young‐of‐year and adult samples revealed no genetic differentiation and no measurable reduction in genetic variation of offspring, indicating little variance in reproductive success and no reduction in effective population size for this year class. Simulation analyses determined that the data set was sufficiently powerful to detect both slight population structure among adults and a small reduction in effective number of breeders contributing to this year class. The findings of high gene flow and low genetic drift have important implications for fisheries management and conservation efforts.

Enzymatic fingerprinting of Arabidopsis pectic polysaccharides using polysaccharide analysis by carbohydrate gel electrophoresis (PACE) - Christopher J. Barton; Louise E. Tailford; Helen Welchman; Zhinong Zhang; Harry J. Gilbert; Paul Dupree; Florence Goubet (Planta, 2006)

Genetic diversity of resistance genes controlling fusarium head blight with simple sequence repeat markers in thirty-six wheat accessions from east asian origin - Zhuping Yang; Jeannie Gilbert; J. Douglas Procunier (Euphytica, 2006)

Snow-contact volcanic facies and their use in determining past eruptive environments at Nevados de Chillán volcano, Chile - K. Mee; H. Tuffen; J. S. Gilbert (Bulletin of Volcanology, 2006)

Maternal mosaicism for mutations in the ARX gene in a family with X linked mental retardation - K. Poirier; J. Abriol; I. Souville; C. Laroche-Raynaud; C. Beldjord; B. Gilbert; J. Chelly; T. Bienvenu (Human Genetics, 2005)

Quantitative trait loci for hip dysplasia in a crossbreed canine pedigree - Rory J. Todhunter; Raluca Mateescu; George Lust; Nancy I. Burton-Wurster; Nathan L. Dykes; Stuart P. Bliss; Alma J. Williams; Margaret Vernier-Singer; Elizabeth Corey; Carlos Harjes; Richard L. Quaas; Zhiwu Zhang; et al. (Mammalian Genome, 2005)

Brachionus calyciflorus is a Species Complex: Mating Behavior and Genetic Differentiation Among Four Geographically Isolated Strains - John J. Gilbert; Elizabeth J. Walsh (Hydrobiologia, 2005)

Strategic approach to mitigating weather induced defects of wheat quality - F. R. Clarke; J. M. Clarke; R. M. DePauw; M. R. Fernandez; S. Fox; J. Gilbert; G. Humphreys; R. E. Knox; T. N. McCaig; D. Procunier; M. Sissons; D. Somers (Euphytica, 2005)

Catchment–coastal zone interaction based upon scenario and model analysis: Elbe and the German Bight case study - J. Hofmann; H. Behrendt; A. Gilbert; R. Janssen; A. Kannen; J. Kappenberg; H. Lenhart; W. Lise; C. Nunneri; W. Windhorst (Regional Environmental Change, 2005)

Effect of sunlight intensity and albinism on the covering response of the Caribbean sea urchin Tripneustes ventricosus - Arthur J. Kehas; Kathleen A. Theoharides; John J. Gilbert (Marine Biology, 2005)

Thuja plicata exclusion in ectomycorrhiza-dominated forests: testing the role of inoculum potential of arbuscular mycorrhizal fungi - Adrian Weber; Justine Karst; Benjamin Gilbert; J. P. Kimmins (Oecologia, 2005)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

Assessment of Water Quality in Association with Land use in the Tillamook Bay Watershed, Oregon, USA - Timothy J. Sullivan; Kai U. Snyder; Erin Gilbert; Joseph M. Bischoff; Mark Wustenberg; James Moore; Deian Moore (Water, Air, & Soil Pollution, 2005)

Inhibition of HER-2 by three independent targeting strategies increases paclitaxel resistance of SKOV-3 ovarian carcinoma cells - Shaker Abuharbeid; Jrgen Apel; Gerhard Zugmaier; Cornelius Knabbe; Martin Sander; Sandra Gilbert; Frank Czubayko; Achim Aigner (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Biogeography and macroecology of phorid flies that attack fire ants in south‐eastern Brazil and Argentina - P. J. Folgarait; O. Bruzzone; S. D. Porter; M. A. Pesquero; L. E. Gilbert (Journal of Biogeography, 2005)
Aim Saevissima group fire ants, Solenopsis richteri and S. invicta , have become serious pests when introduced from Argentina and Brazil to other continents. In South America, Solenopsis are distributed across a great variety of habitats and climates. In North America, S. invicta , introduced free of phorids, now ranges from coast to coast in the south. Success in introducing particular Pseudacteon as agents for the biological control of fire ants has varied across climatic zones. We aimed at assembling all the information about fire ant phorids from Argentina and Brazil, to estimate their richness and geographical ranges, to perform a climatic analysis for these distributions, to define groups and climate‐based communities, and to test and elucidate Rapoport's biogeographical rule. Location Argentina and Brazil (South America). Methods From field and museum collections and historical records, we developed a database of fire ant‐specific phorids throughout their known geographical range. A total of 123 sites with values for 15 climatic variables were mapped between 10° and 38° SL and between 35° and 65° C WL for the presence/absence of phorids. We calculated species richness across all sites combined, and for each phytogeographical region, using rarefaction curves, and ICE and Mmean estimators. We calculated mid‐latitudinal points, geographical ranges and areas for each species. The correlation between mid‐latitudinal point and ranges/areas was tested against a null model generated from the randomization of the raw distributional data. We used several types of multivariate analyses to distinguish groups of phorids by phytogeographical regions, hosts and climate, to find gradients of climate throughout the studied area, to define phorid communities in terms of their relationships with gradients of climate, and to test a mechanism for Rapoport's rule. Results Richness estimations using ICE and Mmean estimators were similar or higher than the observed values depending on the phytogeographical region. Cluster multivariate analyses based on climatic, phytogeographic and host data revealed distinct groupings of Pseudacton . The ‘cerrado’ group was confined to tropical savanna areas. A more ‘widespread’ group included ‘Chaco’ and ‘Maritime’ subgroups defined by their respective association with extreme temperatures or precipitation. Ordination multivariate analyses showed (1) two climatic gradients throughout the study area: one of temperature and the other of precipitation, and (2) that climatic variables significantly explained the observed assemblages of phorids. Positive and negative signs of the eigenvalues from the main axes of a canonical correspondence analysis allowed us to define eight communities whose geographical distribution resembled that of phytogeographical regions. We found a significant and positive correlation between geographical areas and mid latitudinal points, and furthermore, the Mantel test based on climatic variables suggested a mechanism for Rapoport's rule applying in the case of Pseudacteon . Main conclusions Pseudacteon species with greater mid‐latitudinal points occupy broader geographical areas and confront more stressful environmental conditions. Because the composition of Pseudacteon communities is largely determined by climatic variables, the correspondence between climates at sites of origin vs. sites of release should be an important consideration in choosing specific phorids for biocontrol efforts.

The role of halogen substitution in classical cannabinoids: A CB1 pharmacophore model - Spyros P. Nikas; Jolanta Grzybowska; Demetris P. Papahatjis; Avgui Charalambous; Ali R. Banijamali; Ravi Chari; Pusheng Fan; Therapia Kourouli; Sonyuan Lin; Albert J. Nitowski; Gilbert Marciniak; Yan Guo; et al. (The AAPS Journal, 2004)

Parasitoids and competitors influence colony-level responses in the red imported fire ant, Solenopsis invicta - Natasha J. Mehdiabadi; Elizabeth A. Kawazoe; Lawrence E. Gilbert (The Science of Nature, 2004)

Blockade of mesolimbic dopamine D3 receptors inhibits stress-induced reinstatement of cocaine-seeking in rats - Zheng-Xiong Xi; Jeremy Gilbert; Arlene C. Campos; Nicole Kline; Charles R. Ashby; Jim J. Hagan; Christian A. Heidbreder; Eliot L. Gardner (Psychopharmacology, 2004)

From spatial models to spatial evaluation in the analysis of wetland restoration in the Vecht river basin - Alison J. Gilbert; Marjan van Herwijnen; Carolin M. Lorenz (Regional Environmental Change, 2004)

Salinity Effects on Survival, Growth and Morphometry of Four Egyptian Artemia Populations (International Study on Artemia. LXVII) - Nagy El-Bermawi; Athanasios D. Baxevanis; Theodore J. Abatzopoulos; Gilbert Van Stappen; Patrick Sorgeloos (Hydrobiologia, 2004)

Rotifers from diapausing, fertilized eggs: Unique features and emergence - John J. Gilbert; Thomas Schröder (Limnology and Oceanography, 2004)
Sexual reproduction in cyclically parthenogenetic rotifers results in the production of diapausing, fertilized (resting) eggs, which can survive for decades in sediment egg banks. Stem females hatching from these eggs can differ from genetically identical ones produced in subsequent parthenogenetic generations. Differences involve the inhibition of sexual reproduction, which may persist for many parthenogenetic generations; reduced morphology (apterous Polyarthra , shorter‐spined Brachionus ); and larger stores of lipid. These features of stem females may facilitate colonization by favoring population growth via female parthenogenesis and by decreasing food requirements for survival and reproduction. Fertilized eggs in dried sediments probably hatch soon after being flooded by rising water levels. Eggs in permanently submerged sediments may be in environments that inhibit hatching (e.g., darkness, low water temperature, low dissolved oxygen) and hatch only when brought to the sediment surface or resuspended into the water column by currents or bioturbation. Laboratory experiments show that the hatching of diapausing, fertilized eggs can require light and temperatures suitable for population development or specific changes in temperature consistent with a new growing season. The limited data that exist on their emergence from fertilized eggs in natural systems come from sediment traps, from the occurrence in the water column of apterous Polyarthra or empty egg shells, and from calculations of negative mortality rates of planktonic populations. Fertilized eggs often hatch at the beginning of the growth season but may continue to hatch intermittently thereafter. The extremely high genotypic diversity of some natural rotifer populations indicates extensive hatching of stem females from the sediment egg bank.

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

Species Richness and Invasion Vectors: Sampling Techniques and Biases - S. Gollasch; H. Rosenthal; H. Botnen; M. Crncevic; M. Gilbert; J. Hamer; N. Hülsmann; C. Mauro; L. McCann; D. Minchin; B. Öztürk; M. Robertson; et al. (Biological Invasions, 2003)

Remote sensing as a tool for achieving and monitoring progress toward sustainability - Gilbert L. Rochon; Chris J. Johannsen; David A. Landgrebe; Bernard A. Engel; Jonathan M. Harbor; Sarada Majumder; Larry L. Biehl (Clean Technologies and Environmental Policy, 2003)

Raillietiella trachea n. sp., a pentastomid from the trachea of an oriental white-backed vulture Gyps bengalensis taken in Pakistan, with speculation about its life-cycle - J. Riley; J.L. Oaks; M. Gilbert (Systematic Parasitology, 2003)

Modeling carbon to nitrogen and carbon to chlorophyll a ratios in the ocean at low latitudes: Evaluation of the role of physiological plasticity - Nathalie Lefèvre; Arnold H. Taylor; Francis J. Gilbert; Richard J. Geider (Limnology and Oceanography, 2003)
Simulation modeling provides a means for testing the limits of our quantitative understanding of the factors that control phytoplankton biomass, growth rate, and primary productivity in the sea. We simulated the annual cycles of chlorophyll a (Chl a ) concentration, primary productivity, nitrogen export, phytoplankton carbon to nitrogen (C :N) and carbon to Chl a ratios (C : Chl a ) using a physiological model of phytoplankton carbon, nitrogen, and Chl a dynamics. The model was embedded within a one‐dimensional physical model of vertical exchanges that included simple mortality and recycling terms. A sensitivity analysis allowed evaluation of the relative effects of changes in phytoplankton physiology, physical forcing, mortality, and nutrient cycling on Chl a distributions and phytoplankton C: N. Critical to the success of the model was the treatment of mortality, which included seasonal (temperature) and depth‐related components, and the treatment of recycling efficiency, which was considered to be a function of the inorganic nitrogen concentration. The subtropical simulation compared favorably with data obtained at the Bermuda Atlantic Time‐series Study (BATS) station. Our results illustrate the utility of physiological data in validation of biogeochemical models. In particular, model predictions of phytoplankton C: Chl a , which ranged from 30 to 170 g C (g Chl a ) −1 , compared well with direct estimates based on 14 C labeling of Chl a . However, predictions of phytoplankton C: N, which ranged from ~5–9 g C (g N) −1 , could not be verified because of lack of data. This range of C:N suggests a slight limitation of phytoplankton growth rates by nutrients in surface waters.

Specificity of crowding response that induces sexuality in the rotifer Brachionus - John J. Gilbert (Limnology and Oceanography, 2003)
Crowding induced the production of mictic (male‐producing) females in Brachionus calyciflorus from two North American strains and an Australian strain. The specificity of this response to crowding was tested by culturing single individuals of a North American clone in three treatment conditions: a small volume (high density), a large volume (low density), and a large volume with a high density of an Australian clone. The results were consistent and clear in six experiments using different combinations of clones. Crowding low‐density individuals of the North American strains with the Australian strain failed to induce them to produce mictic females. The mictic‐female response in this treatment was similar to that in the low‐density treatment, and both of these responses were significantly lower than that in the high‐density treatment. Since the mictic‐female response to crowding in Brachionus is mediated by a chemical produced by the rotifers themselves, the chemical inducers produced by the Australian and North American strains must be different. Taxonomically specific responses to crowding should increase fitness by assuring that sexual reproduction in the heterogonic life cycle coincides with a high population density of individuals able to mate with one another and, thus, when the production of fertilized resting eggs can be maximized. This would be especially important in plankton communities with diverse rotifer assemblages and multiple congeneric species. Otherwise, a low‐density population of a species could be induced to initiate bisexual reproduction by populations of other species, curtailing its potential for population growth via female parthenogenesis and limiting its production of resting eggs in the future.

Lung Deposition and Pharmacokinetics of Cyclosporine After Aerosolization in Lung Transplant Patients - Gilbert J. Burckart; Gerald C. Smaldone; Michael A. Eldon; Raman Venkataramanan; James Dauber; Adriana Zeevi; Kenneth McCurry; Teresa P. McKaveney; Timothy E. Corcoran; Bartley P. Griffith; Aldo T. Iacono (Pharmaceutical Research, 2003)

Acclimation of white lupin to phosphorus deficiency involves enhanced expression of genes related to organic acid metabolism - Claudia Uhde-Stone; Glena Gilbert; Jane M-F Johnson; Ralph Litjens; Kelly E. Zinn; Stephen J. Temple; Carroll P. Vance; Deborah L. Allan (Plant and Soil, 2003)

Characterization of β‐haemolytic Group B Streptococcus agalactiae in cultured seabream, Sparus auratus L., and wild mullet, Liza klunzingeri (Day), in Kuwait - J J Evans; P H Klesius; P M Gilbert; C A Shoemaker; M A Al Sarawi; J Landsberg; R Duremdez; A Al Marzouk; S Al Zenki (Journal of Fish Diseases, 2002)
Streptococcus agalactiae was isolated from cultured gilthead seabream, Sparus auratus L., and diseased wild Klunzinger's mullet, Liza klunzingeri (Day), in Kuwait Bay, Arabian Gulf. Isolates were catalase negative, β‐haemolytic, Gram‐positive cocci and serogroup B. Experimental infectivity trials with mullet and seabream brain isolates in Nile tilapia, Oreochromis niloticus L., caused 100 and 90% mortality, respectively, within 7 days post‐inoculation indicating virulent S. agalactiae as the bacterial pathogen responsible for the epizootic in Kuwait Bay.

A high degree of genetic diversity is revealed in Isatis spp. (dyer's woad) by amplified fragment length polymorphism (AFLP) - K. Gilbert; S. Garton; M. Karam; G. Arnold; A. Karp; K. Edwards; D. Cooke; J. Barker (Theoretical and Applied Genetics, 2002)

Comparison of Canadian Fusarium graminearum isolates for aggressiveness, vegetative compatibility, and production of ergosterol and mycotoxins - J. Gilbert; D. Abramson; B. McCallum; R. Clear (Mycopathologia, 2002)

The murine perilipin gene: the lipid droplet-associated perilipins derive from tissue-specific, mRNA splice variants and define a gene family of ancient origin - Xinyue Lu; Jasmine Gruia-Gray; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Constantine Londos; Alan R. Kimmel (Mammalian Genome, 2001)

Spatial Economic–Hydroecological Modelling and Evaluation of Land Use Impacts in the Vecht Wetlands Area - J. van den Bergh; A. Barendregt; A. Gilbert; M. van Herwijnen; P. van Horssen; P. Kandelaars; C. Lorenz (Environmental Modeling & Assessment, 2001)

Rotavirus assembly – interaction of surface protein VP7 with middle layer protein VP6 - J. M. Gilbert; N. Feng; J. T. Patton; H. B. Greenberg (Archives of Virology, 2001)

DRV Liposomal Bupivacaine: Preparation, Characterization, and In Vivo Evaluation in Mice - Gilbert J. Grant; Yechezkel Barenholz; Boris Piskoun; Mylarrao Bansinath; Herman Turndorf; Elijah M. Bolotin (Pharmaceutical Research, 2001)

Spine development in Brachionus quadridentatus from an Australian billabong: genetic variation and induction by Asplanchna - John J. Gilbert (Hydrobiologia, 2001)

Observations of insect predation on rotifers - Stephanie E. Hampton; John J. Gilbert (Hydrobiologia, 2001)

In memoriam: W.T. Edmondson (1916–2000) - Robert L. Wallace; John J. Gilbert; Charles E. King (Hydrobiologia, 2001)

Indicators for Transboundary River Management - CAROLIN M. LORENZ; WIM P. COFINO; ALISON J. GILBERT (Environmental Management, 2001)

NONVIRAL GENE TRANSFER INTO PRIMARY CULTURES OF HUMAN AND PORCINE MESOTHELIAL CELLS - J. OHAN; M. A. GILBERT; G. LESECHE; Y. PANIS; P. MIDOUX; L. DROUET (In Vitro Cellular & Developmental Biology - Animal, 2001)

Evidence of homing behavior in the coral reef mysid Mysidium gracile - Benjamin S. Twining; John J. Gilbert; Nicholas S. Fisher (Limnology and Oceanography, 2000)
Mysid swarms at benthic coral reef sites disperse into the water column in the evening and reform at the exact same location the following morning, possibly reflecting homing behavior of individual mysids. To facilitate tracking of individual mysids, we radiolabeled part of a swarm of Mysidium gracile with the gamma‐emitting radioisotope 65 Zn and released the labeled animals back to the focal swarm on a reef in Discovery Bay, Jamaica. We collected the focal swarm and surrounding swarms the next morning to determine the location of the labeled individuals following nighttime dispersal. Seventy‐seven percent of the radiolabeled mysids returned to the same site the next day, and 13% of the labeled individuals were recovered from other nearby swarms. This recovery rate cannot be attributed to random reaggregation and suggests that mysids use a homing behavior to facilitate swarm reformation. This is the first unequivocal evidence of homing behavior in demersal zooplankton.

Characterization of the mouse interleukin-13 receptor α1 gene - Mitsujiro Osawa; Sousuke Miyoshi; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Takashi Hiroyama; Tsutomu Motohashi; Yukio Nakamura; Atsushi Iwama; Hiromitsu Nakauchi (Immunogenetics, 2000)

Molecular cloning and functional characterization of murine Transmembrane Activator and CAML Interactor (TACI) with chromosomal localization in human and mouse - Götz-Ulrich von Bülow; Helen Russell; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Richard J. Bram (Mammalian Genome, 2000)

Influence of the D genome in conferring resistance to fusarium head blight in spring wheat - J. Gilbert; J.D. Procunier; T. Aung (Euphytica, 2000)

Molecular biology and regulation of methane monooxygenase - J. Colin Murrell; Bettina Gilbert; Ian R. McDonald (Archives of Microbiology, 2000)

Direct and indirect effects of juvenile Buenoa macrotibialis (Hemiptera: Notonectidae) on the zooplankton of a shallow pond - Stephanie E. Hampton; John J. Gilbert; Carolyn W. Burns (Limnology and Oceanography, 2000)
We investigated the effects of juvenile Buenoa macrotibialis on the small bodied ( Buenoa over 9–12 d, we found that second and fourth instar Buenoa caused large declines in the copepod Tropocyclops extensus and the rotifer Hexarthra mira . Additionally, populations of several small rotifers increased in the presence of fourth instar Buenoa , probably because of release from Tropocyclops predation, competition, or both.

The Use of Atmospheric Dispersion Models in Risk Assessment Decision Support Systems for Pesticides - Frank A. A. M. de Leeuw; W. Addo J. van Pul; Frederik van den Berg; Andrew J. Gilbert (Environmental Monitoring and Assessment, 2000)

Organization of the mouse microfibril-associated glycoprotein-2 (MAGP-2) gene - Cheryl Frankfater; Erika Maus; Krisztina Gaal; Fernando Segade; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; J. Michael Shipley (Mammalian Genome, 2000)

Summer distribution patterns of the backswimmer, Anisops wakefieldi (Hemiptera: Notonectidae), in a New Zealand pond - John J. Gilbert; Carolyn W. Burns; Caroline C. Gilbert (New Zealand Journal of Marine and Freshwater Research, 1999)
The relative abundance of different‐sized Anisops wakefieldi in a small, fishless pond was determined from sweep‐net samples taken along one open‐water and two shoreline transects at noon on two dates, and at noon and midnight on a third date. During the day, large individuals occurred only along the shore, whereas smaller ones occurred both along the shore and in open water. At night, large individuals also occurred in the open water. The diurnal size‐class segregation suggests that young individuals migrate into less preferred, open water to avoid interference and cannibalism from larger individuals. The shoreline may be preferred during the day because it provides greater food resources or a refuge from visually feeding avian predators. Laboratory experiments in containers with floating aquatic plants at one end complemented the field data. When alone, both small and large A. wakefieldi sought cover during the day and moved into open water at night. During the day, the presence of large individuals induced small ones to move into open water. The results of this study on a notonectid population are consistent with some earlier ones in demonstrating that interactions between large and small size classes may lead to pronounced spatial segregation of size classes, and show for the first time that spatial distributional patterns during the day and night may be very different.

Phenotypic and functional characteristics of porcine peritoneal mesothelial cells - J. Ohan; M. A. Gilbert; J. P. Brouland; J. P. Rougier; G. Trugnan; M. Wassef; G. Leseche; L. Drouet (In Vitro Cellular & Developmental Biology - Animal, 1999)

Regulatory Risk Assessment of Pesticide Residues in Air - A. J. Gilbert (Water, Air, & Soil Pollution, 1999)

The thrombospondin-4 gene - Gail Newton; Stanislawa Weremowicz; Cynthia C. Morton, Nancy A.; Debra J. Gilbert; Neal G. Copeland; Jack Lawler (Mammalian Genome, 1999)

The neurobeachin gene ( Nbea ) identifies a new region of homology between mouse central Chromosome 3 and human Chromosome 13q13 - Debra J. Gilbert; Hartmut Engel; Xiaolu Wang; Karl-Heinz Grzeschik; Neal G. Copeland; Nancy A. Jenkins; Manfred W. Kilimann (Mammalian Genome, 1999)

Some observations on the diet of the backswimmer, Anisops wakefieldi (Hemiptera: Notonectidae) - John J. Gilbert; Carolyn W. Burns (Hydrobiologia, 1999)

Allylmalonamide as a bivalent linker: Synthesis of biantennary GM3-saccharide—Keyhole limpet hemocyanin glycoconjugate and the immune response in mice - Wei Zou; Mary Abraham; Michel Gilbert; Warren W. Wakarchuk; Harold J. Jennings (Glycoconjugate Journal, 1999)

Developing an appropriate strategy to assess genetic variability in plant germplasm collections - J. E. Gilbert; R. V. Lewis; M. J. Wilkinson; P. D. S. Caligari (Theoretical and Applied Genetics, 1999)

Identification of genes within the Krd deletion on mouse Chromosome 19 - Weizhen Ji; Bruce Herron; Julie M. Jones; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Richard Swank; Lorraine Flaherty; Miriam H. Meisler (Mammalian Genome, 1999)

Mixing of floodwaters in a restored habitat wetland in northeastern Ontario - Janice M. Gilbert; Barry G. Warner; Ramon Aravena; J. Chris Davies; Douglas Brook (Wetlands, 1999)

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

Short-term effect of nitrogen enrichment on the microbial communities of a peatland - D. Gilbert; C. Amblard; G. Bourdier; A.-J. Francez (Hydrobiologia, 1998)

Cellular apoptosis susceptibility gene Capts maps to mouse Chromosome 2 - Maria de Miguel; John M. Centanni; Ganesan Gopalan; Debra J. Gilbert; Neal G. Copeland; Nancy A. Jenkins; Peter J. Donovan (Mammalian Genome, 1998)

Mutational analysis of the GDNF/RET-GDNFRα signaling complex in a kindred with vesicoureteral reflux - Sarah E. Shefelbine; Sangeeta Khorana; Pamela N. Schultz; Eileen Huang; Nicole Thobe; Zheng J. Hu; Gary M. Fox; Shuqian Jing; Gilbert J. Cote; R. F. Gagel (Human Genetics, 1998)

Chromosomal location and tissue expression of the gene encoding the adenovirus E1A-regulated transcription factor E4F in humans and mice - Robert J. Rooney; Rachael R. Daniels; Nancy A. Jenkins; Debra J. Gilbert; Kristen Rothammer; Stephan W. Morris; Douglas R. Higgs; Neal G. Copeland (Mammalian Genome, 1998)

Interleukin-1 receptor-associated kinase gene Il1rak maps to the mouse X Chromosome - John M. Centanni; Maria de Miguel; Ganesan Gopalan; Debra J. Gilbert; Neal G. Copeland; Nancy A. Jenkins; Peter J. Donovan (Mammalian Genome, 1998)

Genetic mapping of the galanin-GMAP (Galn) gene to mouse Chromosome 19 - Leticia C. Guida; Philippa Charlton; Debra J. Gilbert; Nancy A. Jenkins; Neal G. Copeland; Robert D. Nicholls (Mammalian Genome, 1998)

Erythroid Krüppel-like transcription factor (Eklf) maps to a region of mouse Chromosome 8 syntenic with human Chromosome 19 - Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Eugenia Gruzglin; James J. Bieker (Mammalian Genome, 1998)

Chromosome localization of two new mammalian kinases related to yeast and fly chromosome segregation-regulators - Ganesan Gopalan; Debra J. Gilbert; Neal G. Copeland; Nancy A. Jenkins; Peter J. Donovan (Mammalian Genome, 1998)

Genomic structure and chrosomal localization of the murine LIM class homeobox gene Lhx1 - Tetsuya A. Fujii; Kveta Cvecklova; Debra J. Gilbert; Neal G. Copeland; Nancy A. Jenkins; Heiner Westphal (Mammalian Genome, 1998)

The genetic origin of mouse annexin VIII - Maria Pilar Fernández; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Reginald O. Morgan (Mammalian Genome, 1998)

Differential sensitivity of Synchaeta and Daphnia to nucleosides from Anabaena affinis - John J. Gilbert (Hydrobiologia, 1998)

Human and murine PTX1/Ptx1 gene maps to the region for Treacher Collins Syndrome - Michael J. Crawford; Christian Lanctôt; Jacques J. Tremblay; Nancy Jenkins; Debra Gilbert; Neal Copeland; Barbara Beatty; Jacques Drouin (Mammalian Genome, 1997)

Assignment of the murine inwardly rectifying potassium channel IRK3 gene (Kcnj4) to the mouse Chromosome 15 - Ken-ichirou Morishige; Toru Takumi; Nachiko Takahashi; Hidekazu Koyama; Hirohisa Kurachi; Akira Miyake; Yuji Murata; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Yoshihisa Kurachi (Mammalian Genome, 1997)

Genomic organization and chromosomal localization of the mouse snail (Sna) gene - Rulang Jiang; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Thomas Gridley (Mammalian Genome, 1997)

Reaction to Fusarium Head Blight of Spring Wheats Based on Symptoms, Fusarium spp. and Mycotoxins - A. Tekauz; J. Gilbert; D. Abramson (Cereal Research Communications, 1997)

Influence of The D Genome in Fusarium Head Blight Resistance - J. Gilbert; T. Aung; J. D. Procunier K (Cereal Research Communications, 1997)

Wide Crosses to Improve Fusarium Blight Resistance in Wheat - George Fedak; K. C. Armstrong; R. C. Sinha; J. Gilbert; J. D. Procunier; J. D. Miller; R. Pandeya (Cereal Research Communications, 1997)

Eyes absent: A gene family found in several metazoan phyla - Melinda K. Duncan; Lidia Kos; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Stanislav I. Tomarev (Mammalian Genome, 1997)

cDNA cloning and chromosomal mapping of mouse fast skeletal muscle troponin T - Anne Koch; Todd S. -C. Juan; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Ian K. McNiece; Frederick A. Fletcher (Mammalian Genome, 1997)

Noise stress does not modulate effects of smoking/nicotine on β-endorphin, cortisol, ACTH, glucose, and mood - D. G. Gilbert; Charles J. Meliska; Louisette C. Plath (Psychopharmacology, 1997)

The glacilacustrine sedimentary environment of Bowser Lake in the northern Coast Mountains of British Columbia, Canada - Robert Gilbert; Joseph R. Desloges; John J. Clague (Journal of Paleolimnology, 1997)

The Mouse Spam1 maps to proximal Chromosome 6 and is a candidate for the sperm dysfunction in Rb(6.16)24Lub and Rb(6.15)lAld heterozygotes - Xiangning Deng; Jennifer Moran; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Paul Primakoff; Patricia A. Martin-DeLeon (Mammalian Genome, 1997)

Toxicologic studies with japanese quail fed winter wheat grown on municipal sludge-amended soil - Gilbert S. Stoewsand; John N. Telford; Judy L. Anderson; Carl A. Bache; Walter H. Gutenmann; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1984)

Indicator organisms and fish and shellfish poisoning - R. J. Gilbert (Antonie van Leeuwenhoek, 1983)

Mercury toxicity as compared to adrenocorticotropin-induced physiological stress in the chicken - J. Paul Thaxton; Jeannine Gilbert; Patricia Y. Hester; John Brake (Archives of Environmental Contamination and Toxicology, 1982)

Safety evaluation of vegetables cultured on municipal sewage sludge-amended soil - Juanell N. Boyd; Gilbert S. Stoewsand; John G. Babish; John N. Telford; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1982)

ThePassiflora problem in Hawaii; prospects and problems of controlling the forest weedP. Mollissima [Passifloraceae] with heliconiine butterflies - J. K. Waage; J. T. Smiley; L. E. Gilbert (BioControl, 1981)

Nutritional and toxicological studies with growing pigs fed aquatic plant rations - Tuan N. Yap; Wilson G. Pond; Jung F. Wu; Gilbert S. Stoewsand; Patricia C. Wszolek; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1979)

Visual discrimination of textures with identical third-order statistics - B. Julesz; E. N. Gilbert; J. D. Victor (Biological Cybernetics, 1978)

Summary of Discussions at a Conference on Rhizoctonia Held at Twin Falls, Idaho, Feb. 24, 1977 - W. J. Hooker; Gilbert J. Banville; A. R. Weinhold; Tully Bowman; D. H. Hall; Gene D. Easton; J. R. Davis; James A. Frank (American Journal of Potato Research, 1978)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

Metabolic changes during sexual differentiation in Allomyces - Milos J. Kobr; Gilbert Turian (Archives of Microbiology, 1967)

Crop and market news - B. A. Brown; H. C. Moore; P. N. Davis; J. F. Sharples; H. O. Werner; O. C. Hicks; J. Gilbert Borton; H. C. Odell; E. V. Hardenburg (American Journal of Potato Research, 1926)

Potato notes - C. Tice; H. G. Zuckerman; W. C. Edmundson; W. L. Floyd; G. W. Waller; A. J. Johnston; E. P. Miller; E. A. Stokdyk; G. L. Tiebout; H. C. Moore; Walter M. Peacock; Andrew Schnetzler; et al. (American Journal of Potato Research, 1925)

Seed potato certification notes - F. H. Harrington; J. Tucker; Alfred H. Gilbert (American Journal of Potato Research, 1924)

Potato notes - C. Tice; A. J. Johnston; E. P. Miller; E. A. Stokdyk; J. W. Weston; A. G. Tolass; J. Norton Woodruff; Ellwood Douglass; Wm. H. Martin; W. S. Blair; N. W. Glines; J. Tucker; et al. (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; E. A. Stokdyk; H. J. Wheeler; J. F. Hockey; H. O. Werner; W. H. Martin; O. G. Bowen; J. Gilbert Barton; Wm. B. Duryee; J. C. Crissey; A. H. C. Odell; C. R. Inglee; et al. (American Journal of Potato Research, 1924)

Certified seed potato notes - J. F. Hockey; E. V. Hardenburg; A. H. Gilbert (American Journal of Potato Research, 1924)

Seed certification notes - M. F. Barrus; W. Stuart; A. W. Tompkins; A. H. Gilbert; J. G. Milward (American Journal of Potato Research, 1924)